Protonated carbon nitride with amino-rich and π-electron delocalized structure for photocatalytic lignin C–C bond cleavage - Jie Xu; Taotao Liu; Yuheng Wang; Ming Li; Ganglin Chen; Yilan Huang; Ge Zhao (Journal of Environmental Chemical Engineering, 2026)

Zn-promoted FeSx/γ-Al2O3 catalyst for stable selective reduction of high-concentration SO2 with methane: synergistic mitigation of carbon and sulfur deposition - Songlin Qu; Tingting Ge; Zhonghao Zhang; Yuxia Li; Yuchao Li; Ming Wang; Haofei Huang; Cuncun Zuo (Fuel, 2026)

A SASP-related four-gene signature associated with intervertebral disc degeneration: integrated bioinformatics analysis and validation of pinocembrin as a therapeutic candidate - Ge-Liang Yao; Shi-Jiang Wang; Ying Zhang; Jia-Ming Liu; Hong-Hai Song; Zhi-Li Liu (Molecular Biology Reports, 2026)

Computational study on the hydrothermal cracking routes of N-cyclohexylnaphthalen-1-amine based on density functional theory - Shao-Xuan Zhong; Wei Li; Jia-Wei Qu; Ming-Lan Ge; Yuan-Liang Yang; Jian-Qiang Tao; Jing Wang (Fuel, 2026)

Chain mail-inspired adaptive protection architecture using mechanically interlocking lattice - Jiahui Ge; Zhenlong Chao; Longtao Jiang; Ming Zhu; Bo Geng; Tian Luo (Engineering Structures, 2026)

Aerodynamic shape optimization of bridge towers based on a hybrid Softplus-Kriging surrogate model: Reducing aerodynamic interference on adjacent hangers - Dian-yi Guo; Wen-ming Zhang; Li-ming Zhao; Yao-jun Ge (Engineering Structures, 2026)

Disruption of progesterone synthesis by PBDEs: Potent inhibition of human and rat placental 3β-hydroxysteroid dehydrogenase by the metabolite 4-Bromodiphenyl ether - Lubin Xie; Qianjin Fei; Ming Su; Yunbing Tang; Yang Zhu; Ren-shan Ge; Ping Duan; Chengshuang Pan (Toxicology and Applied Pharmacology, 2026)

Eco-hydrological processes in controlling vertical and lateral carbon fluxes in a subtropical salt marsh: Insights from modeling and scale-resolved analysis - Ke-Hua Zhu; Li-Shan Tan; Guan-Xun Wang; Li-Ming Xue; Zeng-Feng Li; Hua-Yu Chen; Qing Lyu; Bo-Fei Li; Wei Zhao; Christian Schwarz; Zhen-Ming Ge (CATENA, 2026)

Effects of metal ions and pH on the optical properties of atmospheric brown carbon - Yu Huang; Ruoyuan Lei; Yingying Sha; Haiwei Li; Yunjiang Zhang; Junfeng Wang; Yun Wu; Ming Wang; Jianhuai Ye; Xinlei Ge (Atmospheric Pollution Research, 2026)

Multidimensional evaluation and quantification of tunnel shotcrete roughness using point cloud data - Yun-Jian Cheng; Rong-Feng Chen; Ming-Xing Ye; Wen-Ge Qiu; Feng Lu (Tunnelling and Underground Space Technology, 2026)

Evaluating the collective effects of vertical and ground greening on microclimate and energy consumption in a high-density building array - Dongjin Cui; Ruikun Ge; Xiaolong Zheng; Guozhu Liang; Jian Hang; Cheuk Ming Mak (Sustainable Cities and Society, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

Microbial biofilms succession of aquaculture fouled net under the UV-C antifouling technology - Ming-Shan Sun; Shan Ge; Liu-Yi Huang; Chun-Wei Bi; Xiao Liu (Aquacultural Engineering, 2026)

The JAK/STAT pathway: a pivotal therapeutic target in disease and advances in natural product modulation - Ming-Yue Li; Yu-Yang Lin; Chun-Ying Wang; Yu-Shan Qi; Jun-Sheng Zhang; Di Ge; Hai-Na Yu; Hua Zhang; Jie Bao (Molecular Diversity, 2026)

Rapid prediction of wind field in street canyons with infrastructure elements using neural operators - Guozhu Liang; Ruikun Ge; Dongjin Cui; Jian Hang; Gang Hu; Cheuk Ming Mak (Urban Climate, 2026)

Predefined-time global prescribed performance tracking of ASV via adaptive event-triggered control - Peng Chen; Tao Han; Bo Xiao; Yuan Tan; Xi-Sheng Zhan; Ming-Feng Ge (Ocean Engineering, 2026)

Atmospheric aqueous-phase reactions of organics in dark: A review - Yingying Sha; Ruoyuan Lei; Ziyan Zou; Junfeng Wang; Yunjiang Zhang; Haiwei Li; Yun Wu; Ming Wang; Xinlei Ge (Atmospheric Environment, 2026)

Neuroprotective Effects of PNU-282,987, an α7-Nicotinic Receptor Agonist, on Sevoflurane-Induced Pyroptosis and Cognitive Impairment in Rats - Jun Xu; Xufang Sun; Dedong Xu; Yuan Ge; Lei Ming (Journal of Pharmaceutical Innovation, 2026)

Characterization of an Endophytic Fusarium odoratissimum Strain 25# from Dysosma versipellis with Putative Podophyllotoxin Production - Xiao-Ming Tan; Zheng-Hu Guo; Xiang-Hua Xia; Xin-Yi Xie; Wen-Tao Tan; Chang-Ge Yuan; Yun-Sheng Wang; Ya-Qin Zhou (Current Microbiology, 2026)

Integrative multi-omics reveals NQO1-mediated airway epithelial injury as a key mechanism of bisphenol A–induced COPD - Rui Li; Shaobo Ge; Jin Liu; Yuer Li; Shiyuan Yao; Shuhan Ma; Yuanliang Sun; Xiao Li; Xia Yang; Jie Zhang; Ming Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Liquid-liquid phase separation-driven enzyme catalysis for efficient biosynthesis of isoprenoid natural products - Han Wang; Bing-Bing Ma; Fei Cao; Ji-Jin Xie; Bei-Bei Wang; Shao-Yong Zhang; Ji-Dong Wang; Zha-Jun Zhan; Yu-Mei Ge; Xu-Ming Mao (Science China Life Sciences, 2026)

Pear PbrPRKs regulate pollen tube growth via modulation of apical actin and reactive oxygen species homeostasis - Lan Xu; Yuzhen Qian; Yusheng Xu; Haoran Wu; Juan Ma; Jitao Ge; Yuqian Wang; Kaijing Zhang; Yihu Sui; Xueping Zhang; Jingjing Qian; Shuangshuang Jia; et al. (Plant Science, 2026)

Distributed nonlinear placement problems in the NASVs with nonsmooth objectives and unknown time-varying actuator faults - Wen-Jin Liu; Rui-Qi Cao; Xinxin Zhang; Xiang-Yu Yao; Ming-Feng Ge (Ocean Engineering, 2026)

Iron-based nanozymes: From mechanisms to functional applications - Jia-Ming Wang; Kai-Zheng Feng; Pu-Ge Yu; Haoan Wu; Ming Ma; Yu Zhang (Chemical Engineering Journal, 2026)

Resilience assessment of metro-bus composite networks under sudden disruptions integrating passenger behavior - Yuanwen Lai; Yuchen Ge; Shiqi Zhang; Ming Guan; Said M. Easa; Shuyi Wang (Transportation Research Part D: Transport and Environment, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

A physics-informed hybrid framework for dynamic wellhead pressure prediction and equipment safety assessment in high-temperature high-pressure condensate gas wells - Lu Zou; Ming Tang; Shiming He; Taiheng Zhang; Ge Wang; Xinyu Guo; Xuliang Zhang; Huajun Li (Process Safety and Environmental Protection, 2026)

Safe path planning and fault-tolerant formation control of NMSVs under cyber and actuator failures - Zhi-Kui Wang; Teng-Fei Ding; Ming-Feng Ge; Chang-Duo Liang (Ocean Engineering, 2026)

Three new polyketides isolated from the Karst cave-derived Streptomyces sp. FD-2-6 - Xuehao Hu; Xiu Yang; Liangqun Li; Lijuan Ge; Qiji Li; Xiaosheng Yang; Juan Yang; Ming Gao (Natural Product Research, 2026)

Global trends in coastal aquaculture ponds: navigating seafood demand and ecological conservation - Dehua Mao; Duanrui Wang; Ming Wang; Hong Yang; Julian R. Thompson; Xiangming Xiao; Yujia Zhang; Kaishan Song; Chunying Ren; Juhua Luo; Ling Luo; Ge Liu; et al. (Science Bulletin, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Unraveling the synergy of wheat-based probiotic- fermented modified dietary Fibers, resistant starch, and gluten in constructing high-quality, low Glycemic index noodles - Ai-Mei Liao; Xiao-ge Liu; Qiao-Qiao Lai; Jia-qi Wang; Kiran Thakur; Long Pan; Yin-Chen Hou; Na Liu; Xian-ming Liu; Zhao-Jun Wei (Food Chemistry, 2026)

Multi-omics characterization of benzo[a]pyrene toxicity networks identifies SERPINE1 and STK3 as prognostic biomarkers and therapeutic targets in head and neck squamous cell carcinoma - Yan Guo; Jiarui Zhang; Jingchun Ge; Liang Li; Ming Liu; Linli Tian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

RNA interference with the selenoprotein M gene inhibits the growth promoting effect by selenium supplementation to silkworm Bombyx mori - Run-Hui Ma; Wen-Jie Ge; Fei Hu; Ting-Ting Hong; Kiran Thakur; Shun-Ming Tang; Zhao-Jun. Wei (Journal of Asia-Pacific Entomology, 2026)

Alleviating effects and mechanism of Lacticaseibacillus paracasei BHP06 on the allergic reactions induced by ovalbumin - Xiang-Ge Xin; Yue Meng; Jun Meng; Jun Xi; Chang-He Ding; Rui-Han Ge; Yu-Tong Bai; Ming-He Li (Food Bioscience, 2026)

Ecological effects and strategies of Spartina alterniflora Loisel. removal in China - Zhanbin Luo; Fu Chen; Xi-En Long; Jing Ma; Jiyou Wei; Yudi Guo; Yanfeng Zhu; Yongjun Yang; Xiaoping Ge; Yanyan Kang; Ming Zou; Lei Liu; et al. (Environmental Impact Assessment Review, 2026)

Cytoplasmic-nuclear remote suppression of c-MYC induces cell cycle arrest and enhances radiotherapy sensitivity in liver cancer via biohybrid platelets - Lin Xiao; Fei Ge; Qinyu Ji; Rui Ji; Yan Wang; Shaoqing Ju; Ming Cui; Donglin Xia; Rongrong Jing (Chemical Engineering Journal, 2026)

In-situ cultivation and process dynamics of algal-bacterial granular sludge in a continuous-flow self-circulation reactor - Wei-Kang Qi; Yu-Ge Sun; Ming-Ming Zhang; Rui Hu; Yong-Zhen Peng; Cong Wang (Bioresource Technology, 2026)

Tidal irrigation-based rice cultivation enhances coastal blue carbon and decreases GHG emissions in brackish mudflats - Lang Zhang; Linlin Li; Hualei Yang; Wenbang Tang; Ji Chen; Hongkai Zhou; Ying Huang; Xuechu Chen; Xiuzhen Li; Ming Luo; Xingyun Huang; Faming Wang; et al. (Agricultural and Forest Meteorology, 2026)

Photo-responsive polyprodrug supramolecular assemblies with self-accelerated subcellular delivery for synergistic photochemotherapy - Ming Liu; Zhenduo Zhao; Ming Li; Yitian Chen; Yicheng Wang; Xuehua Lin; Xinyu Wang; Qinghao Zhou; Zhishen Ge; Yongan Tang; Yibin Deng; Yuliang Zhao; et al. (Science Bulletin, 2026)

Evidence of heterogeneity in the mantle source of Quaternary Naozhou Island basalts from REEs and Sr-Nd-Pb isotopes - Cui Xiao-Ge; Li Zhi-Hua; Xie Shi-Xiong; Yang Wen-Jian; Wang Ming-Qiu; Cheng Liu-San; Gao Cai-Xia; Jiang Hong-Liang (Lithos, 2026)

Exogenous melatonin alleviates heat stress-induced metabolic slowdown affecting broiler growth by improving lipid metabolism - Fei Song; Binglin Wang; Xin Kang; Aige Han; Huiyuan Rui; Xiangyang Xu; Yi Guo; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2026)

Plasma MicroRNA and Protein Signature Associated with Obesity in the Chinese Han Population Using MicroRNA Omics and Proteomics Analysis of 1026 Subjects - Yun-Xia Xie; Jian-Ge Qiu; Zhao-Hui Yang; Chen Ding; Le-Ming Shi; Si-Jia Wang; Li Jin; Bing-Hua Jiang (Phenomics, 2026)

Operational strategy and impact analysis of single train isolation in high pressure heater system for generation III pressurized water reactors - Xu Jiaoshen; Qin Ge; Li Dongyuan; Liu zhiyun; Wang Ming; Li Qiang (Annals of Nuclear Energy, 2026)

Integrated items safety classification method considering risk evaluation for nuclear reactors - Ming Sun; Xiaoer He; Longlong Tao; Shaoxuan Wang; Daochuan Ge; Chenglong Cao; Zhongchang Zhang (Annals of Nuclear Energy, 2026)

Attached microalgae-simulated plants enhanced multiple-pollutant removal in a tidal flow constructed wetland: quantified efficiencies, pathways, and biological mechanisms - Shu-Han Ge; Mei-Zi Yang; Wei-Yi Qian; Lin-Lan Zhuang; Hai-Ming Wu; Zhuo Chen; Xiao-Xiong Wang; Jian Zhang (Water Research, 2026)

Copper exposure induces autophagy and angiogenesis in liver cell via ATF4 activation independent of TFEB - Meng Zhang; Yi-Ge Zhang; Yu-Tian Shi; Xiao-Chuan Qu; Yu-Heng Li; Ji-Xing Miao; Guo-Ming Sun; Peng Ge; Bao-Qin Liu (Toxicology, 2026)

Metabolic activation of pentachlorophenol: TCBQ as a potent inhibitor of gonadal steroidogenesis via 3β-hydroxysteroid dehydrogenase NAD+ binding-site thiolalkylation - Yao Lv; Jingwei Zhang; Ming Su; Shun Lu; Shaowei Wang; Ren-shan Ge; Huitao Li (Reproductive Toxicology, 2026)

Naringenin as a bioactive preservative: Coordinated suppression of ethylene biosynthesis and cell wall disassembly delays apple senescence during storage - Ming-Fei Qiao; Peng-Liang Han; Meng-Meng Wei; Zhao-Peng Nie; Song Zhang; Wen-Yan Wang; Hai-Bo Wang; Tian-Ge Chu; Ze Chen; Quan Sun; Da-Gang Hu (Postharvest Biology and Technology, 2026)

Highly oxidized germacrane-type sesquiterpenoid dimers from Elephantopus tomentosus L.: Structural characterization, DFT calculation and anti-hepatoma potential - Zi-Hao Ge; Si-Hui Mi; Wen-Long Kou; Guo-Dong Yao; Bin Lin; Jian Wang; Ming Bai; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2026)

Chemical characteristics of fine aerosols and associated speciated organic compounds in summer Nanjing, China - Yuanjie Shan; Daoming Li; Shijie Cui; Jiukun Xian; Yunjiang Zhang; Junfeng Wang; Haiwei Li; Ming Wang; Yun Wu; Xinlei Ge (Journal of Environmental Sciences, 2026)

Compact-pol to quad-pol SAR reconstruction via a joint mathematical-physical-constrained multimodal correlation-preserving latent diffusion framework - Zihuan Guo; Hong Zhang; Ji Ge; Xiao-Ming Li; Peifeng Ma; Haoxuan Duan; Lu Xu; Chao Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Copper mediates oxidative stress and immune response in snakehead (Channa argus) through Nrf2 and NF-κB pathway - Xue-qin Wu; Ming-ze Li; Lu Lu; Xiu-mei Chen; Xiao-tian Niu; Yi-di Kong; Gui-qin Wang; Chang-ge Xia; Min Li (Fish & Shellfish Immunology, 2026)

Corrigendum to “Dendrobium officinale polysaccharide promotes M1 polarization of TAMs to inhibit tumor growth by targeting TLR2” [Carbohydrate Polymers 292 (2022) 119683] - Hong-Yan Wang; Ji-Chun Ge; Feng-Yun Zhang; Xue-Qiang Zha; Jian Liu; Qiang-Ming Li; Jian-Ping Luo (Carbohydrate Polymers, 2026)

Causal Links Between the Plasma Lipidome and Cognitive Performance: Targets, Pathways, and Lifestyle Influences - Ran Miao; Qian Wang; Si-liang Ge; Ming Chen; Feng Zhao; Wei-dong Mi; Jiang-bei Cao (Molecular Neurobiology, 2026)

Dual-functional carbon materials for sustainable Cr(VI)-organic co-decontamination: Structure activity relationship analysis of defect and oxygen content - Ming Zhang; Qingkai Shi; Jing Tong; Min Cheng; Hao Ge; Sai Li; Guangfu Wang; Li Du; Hongda Liu; Ao Chen; Zhongwu Li (Journal of Environmental Chemical Engineering, 2025)

Developing a multi-scale adaptive generalized morphological filtering algorithm for denoising ocean wave-induced interference in marine electromagnetic data - Jianxin Pei; Yanyan Lu; Zhijun Du; Ming Luo; Gongyi Sun; Jiaqi Ge (Journal of Applied Geophysics, 2025)

Statistical inferences of differences and correlations in the seismic frequencies of large-scale fault zones in Western Sichuan, China - Yuan Xue; Dan Hu; Junreng Ge; Xinyu Yao; Mingyue Dai; Bingyan Fan; Yu Ming; Muchen Lin (Journal of Seismology, 2025)

mTORC1 regulates the proliferation of SOX9+ porcine skin-derived stem cells (pSDSCs) by promoting S6K phosphorylation - Ming-Xin Zang; Geng Zhang; Ying Zhang; Sha-Sha Wang; Xiang-Wei Zhai; Na Zhao; Wei Ge; Jin-Wen Xie; Wei Shen; Shun-Feng Cheng (Histochemistry and Cell Biology, 2025)

Strategic fertilization enhances crop quality index via changes in soil microbial generalist communities - Haosheng Du; Yaoyao Tong; Hongwei Liu; Zhaofeng Yuan; Haoqing Zhang; Xianqing Zheng; Yangwu Deng; Ming Chen; Tida Ge (Applied Soil Ecology, 2025)

Predefined-time distributed optimal formation control of networked marine surface vehicles based on a nonsingular segmented terminal sliding mode method - Chang-Duo Liang; Yang Zhang; Qian Chen; Teng-Fei Ding; Ming-Feng Ge (Ocean Engineering, 2025)

A study on prediction of radioactive fallout based on the WRF-NAQPMS model - Feifei Li; Qiang Liu; Wei Liu; Zhaoru He; Baozhu Ge; Ying Zhang; Nuohang Liu; Yangchao Li; Ming Yang (Journal of Environmental Radioactivity, 2025)

Experimental study, finite element simulation and theoretical analysis on punching shear capacity of steel-ECC composite slabs - Youzhu Lin; Di Yao; Ge Gao; Tianfei Gu; Ming Sun; Jiachuan Yan (Engineering Structures, 2025)

Boosting photochromism and room-temperature-phosphorescence for multi-dimensional dynamic encryption via donor–acceptor anion–π interaction - Yang Hua; Jian-Ge Zeng; Chun-Jie Liu; Ming-Sheng Wang; Li Li (Chemical Engineering Journal, 2025)

High-performance large-area ITO-free organic photovoltaics under indoor illumination enabled by a dual-interfacial engineering strategy - Jiaxin Gao; Zheng Li; Cuifen Zhang; Fangliang Dong; Zheng Tang; Ming Wang; Dengteng Ge; Zaifei Ma (Chemical Engineering Journal, 2025)

Intermediate-entropy metal hexagonal nanoplates for high-performance and durable formic acid electrooxidation - Shengming Li; Hu Yang; Xin Cheng; Jie Zheng; Yuan Liu; Chengwei Deng; Feng Ji; Sisi Liu; Ming Ge; Xiaolei Yuan (Chemical Engineering Journal, 2025)

Maximum incremental reactivity for volatile organic compounds in three city clusters of China: quantification, variability, and implications for ozone control - Ming Wang; Yunlang Lu; Wenhao Ji; Wenxuan Chai; Hongli Wang; Feng Ding; Xin Zhao; Momei Qin; Yunjiang Zhang; Xinlei Ge; Min Shao (Atmospheric Environment, 2025)

Bio-derived phytic acid synergistic peptide decorated polyamide membrane for enhanced permeance and antimicrobial properties - Mianliang Ji; Zihao Ge; Kun Wang; Yinshan Xie; Hulin Li; Jian Li; Ming Xie (Water Research, 2025)

Corrigendum to “Microwave ultra-narrow band antenna sensor based on TiO2/MXene for room-temperature acetone detection” [J. Environ. Chem. Eng. 13 (5) (2025) 118803] - Jie Wei; En-Kang Wu; Ji-Hao Zhang; Zhen Zhang; Xiao-Cong Tang; Tian Qiang; Yongwoo Jang; Xiao-Feng Gu; Meng Zhao; Svetlana von Gratowski; Jun-Ge Liang; Ming-Yang Yan; et al. (Journal of Environmental Chemical Engineering, 2025)

Microwave ultra-narrow band antenna sensor based on TiO2/MXene for room-temperature acetone detection - Jie Wei; En-Kang Wu; Ji-Hao Zhang; Zhen Zhang; Xiao-Cong Tang; Tian Qiang; Yong-Woo Jang; Xiao-Feng Gu; Meng Zhao; Svetlana von Gratowski; Jun-Ge Liang; Ming-Yang Yan; et al. (Journal of Environmental Chemical Engineering, 2025)

Effect of MnFe2O4 loading on photocatalytic performance of BiVO4 for levofloxacin degradation with or without peroxydisulfate - Meng Tang; Liduan Zhang; Lijia Zheng; Ming Li; Ming Ge (Environmental Research, 2025)

Biogeomorphology and carbon sequestration in a coastal shoal invaded by Spartina alterniflora in the Yangtze Estuary: 22-year simulation for management implication - Ke-Hua Zhu; Zhen-Ming Ge; Ying Huang; Lei-Hua Zhao; Zeng-Feng Li; Wei Zhao; Hua-Yu Chen; Dan Zhang; Hai-Feng Cheng; Wei Zhang; Pei Xin (Ecological Engineering, 2025)

Potential tuning of polycrystalline piezoelectric component for effective energy-band structure and markedly enhanced H2 yield of photocatalytic component - Xinxin Jin; Yingshuang Zhang; Xiao Li; Peng Liu; Qinghao Ge; Zhihao Zhao; Xingzhang Li; Lige Gong; Zhiping Zhang; Dan Li; Feng-Ming Zhang; Limin Dong; et al. (Chemical Engineering Journal, 2025)

Construction of metal-organophosphate (MOPMs) interlayers for preparing high-performance polyamide composite nanofiltration membranes - Jian Li; Tianyu Tang; Mianliang Ji; Fei Liu; Kun Wang; Zihao Ge; Ming Xie (Chemical Engineering Journal, 2025)

Neural Responses to Hypoxic Injury in a Vascularized Cerebral Organoid Model - Yang Li; Xin-Yao Sun; Peng-Ming Zeng; Zhen-Ge Luo (Neuroscience Bulletin, 2025)
Hypoxic injury (HI) in the prenatal period often causes neonatal neurological disabilities. Due to the difficulty in obtaining clinical samples, the molecular and cellular mechanisms remain unclear. Here we use vascularized cerebral organoids to investigate the hypoxic injury phenotype and explore the intercellular interactions between vascular and neural tissues under hypoxic conditions. Our results indicate that fused vascularized cerebral organoids exhibit broader hypoxic responses and larger decreases in panels of neural development-related genes when exposed to low oxygen levels compared to single cerebral organoids. Interestingly, vessels also exhibit neural protective effects on T-box brain protein 2 + intermediate progenitors (IPs), which are markedly lost in HI cerebral organoids. Furthermore, we identify the role of bone morphogenic protein signaling in protecting IPs. Thus, this study has established an in vitro organoid system that can be used to study the contribution of vessels to brain injury under hypoxic conditions and provides a strategy for the identification of intervention targets.

Corrigendum to “Bio-derived phytic acid synergistic peptide decorated polyamide membrane for enhanced permeance and antimicrobial properties” [Water Research 285 (2025) 124021] - Mianliang Ji; Zihao Ge; Kun Wang; Yinshan Xie; Hulin Li; Jian Li; Ming Xie (Water Research, 2025)

Comparative analysis of phytoplankton community structure and stability in the Arabian Sea and Bay of Bengal using eDNA metabarcoding - Changwen Li; Ge Xiao; Han Long; Tongxi Ai; Fenghua Tang; Jianfeng Ju; Shenglong Yang; Yan Pi; Lei Gao; Lingbo Ma; Wei Fan; Ming Zhao; et al. (Marine Environmental Research, 2025)

Role of circular RNAs in formaldehyde-induced lung Injury: Insights into expression and regulatory pathways - Pan Ge; Xiang Zhang; Yan-qi Yang; Jia-ming Xie; Mo-qi Lv; Ying Sun; Ya-zhao Li; Yuan-yuan Geng; Jian Zhang; Dang-xia Zhou (Food and Chemical Toxicology, 2025)

Long-term early warning threshold estimation of landslide deformation in reservoir area through multi-objective optimization inversion - Yi Li; Erfeng Zhao; Chenfei Shao; Yanxin Xu; Haifeng Huang; Peng Ge; Ming Chen (Engineering Geology, 2025)

Degradation-induced changes in soil nutrient availability alter leaf and root traits and their coordination in a riparian wetland ecosystem - Junxiang Ding; Ming Dou; Wenjing Ge; Yingshu Cao; Xiaoying Guo; Yue Yin; Guangsheng Zhou; Deliang Kong; Mei Liu (Plant and Soil, 2025)

Effects of reversing the light-dark cycle on growth performance and intestinal health in heat-stressed broilers - Huiyuan Rui; Xiangyang Xu; Fei Song; Aige Han; Meiwei Lv; Xin Kang; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2025)

Multiple competitive superiority made a great successful invasion of Spartina alterniflora in Eastern China: hints for management - Shi-Hua Li; Zhen-Ming Ge; Li-Shan Tan; Li-Na Xie; Ya-Lei Li (Journal of Environmental Management, 2025)

A point-of-care SERS-based microdevice for multi-pesticide poisoning diagnostics towards first aid scenarios - Meng Jin; Hui Pan; Ge Gao; Mengping Zhang; Haiyan Wei; Xiao Meng; Wenwen Chen; Xinya Zhang; Ming Shang; Cuijuan Wang (Chemical Engineering Journal, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Transcriptome-Wide Sequencing Identifies Non-Coding RNAs and Their Competing Endogenous RNA Networks During the Stages of pPGCLCs-Induced Differentiation - Zhan-Zhong Qiao; Qiu-Yuan Pang; Chang Xu; Xin-Lei Feng; Ming-Xin Zang; Ping Wang; Ying Zhang; Yong-Chao Liu; Qian-Ru Han; Wei Shen; Wei Ge; Shun-Feng Cheng (Stem Cell Reviews and Reports, 2025)

Aqueous production of sulfur-containing aerosols from nitroaromatic compounds and SO2 in wintertime urban haze - Ning Yang; Junfeng Wang; Daniel J. Jacob; Jianhuai Ye; Ming Sheng; Mutong Niu; Yiming Qin; Xinlei Ge; Yele Sun; Zifa Wang; Yuhang Wang; Fengchang Wu; et al. (Science Bulletin, 2025)

Regional fingerprint, enrichment and flavor contribution of Bacillus community in Daqu for Chinese Baijiu - Chutian Zhu; Junlin Wei; Yong Yang; Xiangyang Ge; Ming Yang; Qun Wu; Yongguang Huang (Food Research International, 2025)

Flexible, scalable, and bifunctional MOF-based nanofibrous membranes with gems-on-string structure for simultaneous efficient water evaporation and pollution remediation - Song Ge; Jun Song; Jichao Zhang; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Heterogeneity of Pore Structure in Braided River Delta Tight Sandstone Reservoirs: Implications for Tight Oil Enrichment in the Jurassic Badaowan Formation, Central Junggar Basin - Daiqi Ming; Xiangchun Chang; Fengkai Shang; Pengfei Zhang; Youde Xu; Yansheng Qu; Weizheng Gao; Tianchen Ge; Hongkang Zhao (Natural Resources Research, 2025)

Invasion of Spartina species enhance blue carbon functions by increasing CO2 uptake and reducing methane emissions in Chinese and Danish coastal wetlands - Ming Ge; Linjing Ren; Dan Yang; Xiuzhen Li; Ying Huang; Jianwu Tang; Hans Brix (Journal of Cleaner Production, 2025)

Bio-organic fertilizer enhances soil mineral solubilization, microbial community stability, and fruit quality in an 8-year watermelon continuous cropping system - Yaoyao Tong; Xianqing Zheng; Hongwei Liu; Haoqing Zhang; Yangwu Deng; Ming Chen; Weiguang Lv; Jianping Chen; Tida Ge; Zhaofeng Yuan (Biology and Fertility of Soils, 2025)

Inheritance or Recruitment? The Assembly Mechanisms and Functional Dynamics of Microbial Communities in the Life Cycle of a Wood‐Feeding Beetle - Si‐Xun Ge; Yi‐Ming Niu; Li‐Li Ren; Shi‐Xiang Zong (Molecular Ecology, 2025)
Microbial partners enhance the metabolic capabilities of insects, enabling their adaptation to diverse ecological niches. Xylophagous insects have larvae that can digest lignocellulose and cope with plant secondary metabolites (PSMs). However, there is little information in terms of microbiome sources, dynamics and species contributions. This limits our understanding of the interaction between xylophagous insects and the microbiome. Monochamus saltuarius (Cerambycidae) is a significant borer of conifers. We used combined qPCR, host genomic and microbiome metagenomic datasets, as well as in vitro validation experiments to study the dynamics of the associated microbiome and its interactions with M. saltuarius . We evaluated microbial metabolic/biosynthetic contributions and validated their related functions. Our findings revealed that insect growth and development altered the quantity and community composition of associated bacteria and fungi. The egg microbiome was particularly susceptible to alteration due to oviposition pits. Bacterial transmission largely persisted between developmental stages, while fungal re‐acquisition primarily originated from the external environment. By reconstructing community pathway maps, we identified the cooperative interactions between the insect and its gut microbiome. As larvae transitioned from phloem to xylem feeding, the functional role of the gut microbiome in various pathways was weakened. Remarkably, high‐contribution bacterial species largely overlapped across different functional roles, and these species also showed considerable overlap between phloem and xylem feeding periods. Overall, our study highlights the unique interaction between xylophagous insects and their microbiome, which enhances their ability in lignocellulose digestion, PSMs degradation and the acquisition of essential amino acids, as well as vitamins.

Study on the hydrodynamic characteristics of an outboard engine propeller with hydrophobic coating - Xiaoqing Tian; Haofan Ge; Huachen Pan; Ming Lv; Zefei Zhu; Hao Xu; Jianxing Leng; Chizhong Wang (Ocean Engineering, 2025)

Promotion of symbiotic interaction between phagotrophic protists and beneficial bacteria, mediated via a balancing of soil nutrients, reduces the incidence of watermelon Fusarium wilt - Yaoyao TONG; Li WANG; Chuanfa WU; Haoqing ZHANG; Yangwu DENG; Ming CHEN; Xianqing ZHENG; Weiguang LÜ; Jianping CHEN; Tida GE (Pedosphere, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Puerarin modulates the P62-Keap1-NRF2 pathway and enhances CA7 function to inhibit ferroptosis in ethanol-induced gastric mucosal injury - Xinran Liu; Jiayi Ge; Ximing Yang; Zhihui Chang; Xiaoyu Ma; Shuzhen Cheng; Ming Du (Food Bioscience, 2025)

TGF-β/SMAD Pathway Mediates Cadmium Poisoning-Induced Chicken Liver Fibrosis and Epithelial-Mesenchymal Transition - Jinyang Zhang; Yiming Sun; Miao Yu; Yihan Hu; Xiaodan Huang; Guijun Yang; Ruili Zhang; Ming Ge (Biological Trace Element Research, 2025)

CO2 emission from soil inorganic C in coastal croplands of the Yangtze Delta - Jun Cui; Ming Nie; Shuang Wang; Zhenke Zhu; Gongle Shi; Yakov Kuzyakov; Tida Ge (Agriculture, Ecosystems & Environment, 2025)

Chronic sublethal exposure to chlorantraniliprole inhibits growth and development by disrupting the sugar and fatty acid metabolism in Spodoptera frugiperda - Xiao-Guang Liu; Qing-Ge Wang; Xiao-Ming Liu; Xiang Li; Meng-Fang Du; Cai-Hong Tian; Yun-Hui Zhang; Shi-Heng An (Pesticide Biochemistry and Physiology, 2025)

RNA interference targeting β-N-acetylhexosaminidase genes impairs molting and development of Tetranychus urticae - Ming Liu; Qianwen Wang; Bin Lai; Yan Chen; Rongchumu Ge; Shuo Yan; Chunya Bu (Pesticide Biochemistry and Physiology, 2025)

Environmentally relevant concentrations of DBDPE (decabromodiphenyl ethane) induce intestinal toxicity in silkworms (Bombyx mori L.) - Xue Luo; Rui Xing; Man Xu; Hui-Jun Jiang; Yu-Rui Wang; Ming-Yue Hu; Hao Zhang; Feng Ge; Wei Zhang; Hong-Wei Wang (Environmental Pollution, 2025)

LPA reduces the apoptosis of cryopreserved porcine skin-derived stem cells by inhibiting the regulatory factor TNF-α - Xin-Xiang Xie; Jia-Dong Sun; Ming-Xin Zang; Geng Zhang; Chun-Xiao Li; Xiang-Wei Zhai; Wei Shen; Wei Ge; Shun-Feng Cheng (Cryobiology, 2025)

circTP63-N suppresses the proliferation and metastasis of nasopharyngeal carcinoma via engaging with HSP90AB1 to modulate the YAP1/Hippo signaling pathway - Dan Wang; Sicheng Zuo; Junshang Ge; Hongke Qu; Jie Wu; Na Yi; Lei Shi; Yumin Wang; Yongzhen Mo; Chunmei Fan; Yi He; Pan Chen; et al. (Science China Life Sciences, 2025)

Selenium Treatment Alleviates the Inhibition Caused by Nep-L Gene Knockdown in Silkworm (Bombyx mori) - Ting-Ting Hong; Fei Hu; Wen-Jie Ge; Rui Zhang; Juan Du; Kiran Thakur; Shun-Ming Tang; Zhao-Jun Wei (Biological Trace Element Research, 2025)

Roles of ecological and hydrological processes in the variability of carbon fluxes in a salt marsh of the Yangtze Estuary: Model simulations vs. measurements - Ke-Hua Zhu; Zeng-Feng Li; Wei Zhao; Li-Ming Xue; Hua-Yu Chen; Qing Lyu; Shi-Xian Liu; Zhen-Ming Ge (Agricultural and Forest Meteorology, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

Dynamics of biogeomorphology and CO2 sequestration in Jiangsu’s coastal salt marshes in East China following Spartina alterniflora invasion during 2011 2022 - Zeng-Feng Li; Ke-Hua Zhu; Wei Zhao; Hua-Yu Chen; Zeng Zhou; Zhen-Ming Ge (Regional Studies in Marine Science, 2025)

Variability increased underneath growth enhancement of Mongolian pine natural forests in northeastern China in response to climate change - Ming-Yong Li; Miao Wang; Na Li; Jin-Nan Ge; Guang-You Hao (Forest Ecology and Management, 2025)

Engineered silicon-titania heterojunction elicits catalytic cancer cell death - Deliang Xu; Tingting Xu; Min Ge; Shibo Cao; Zhaoda Yu; Zhixin Chen; Ya-Xuan Zhu; Zhuang Liu; Ming Zong; Han Lin; Jianlin Shi (Chemical Engineering Journal, 2025)

Characterization and sources of volatile organic compounds in a provincial capital city of northern China in 2019–2024: Impact of public events - Haoxin Sui; Houyong Zhang; Yisheng Zhang; Wenxin Tao; Xing Peng; Xuan Ge; Sufan Zhang; Ming Wang; Xiaofei Qin; Mingyue Du; Jinhua Du; Dasa Gu (Atmospheric Environment, 2025)

2-Ethylhexyl diphenyl phosphate induces lung oxidative stress and pyroptosis in chicks - Yiming Sun; Ruili Zhang; Jiali Li; Yihan Hu; Haolin Zhang; Xiangjie Wang; Yi Yang; Haibin Wang; Ming Ge (Science of The Total Environment, 2025)

Characteristic analysis and diagnosis method optimization of scroll compressor pressure pulsation signal under voltage fluctuation - Yanjie Zhao; Tonghe Zhang; Yongxing Song; Qiang Liu; Lin Liu; Ming Yu; Yi Ge (International Journal of Refrigeration, 2025)

Bio-Based aerogel beads with multistage pore network structure for Cr(VI) removal using ice template method - Ya-Ge Wu; Qi Cao; Shuang Dai; Jing Zhao; Ya-Juan Cai; Chuan-Zhe Zhao; Zi-Hao Yang; Yi-Xing Sun; Ting Yue; Ke-Xiao Sang; Jing-Gang Gai; Ming-Ju Tao (Chemical Engineering Journal, 2025)

Zr4+-doped PVA-based fiber films: Enhanced mechanical properties, degradability, and applications in green energy - Song Xue; Wenjing Qin; Changshun Gu; Mengyao Chen; Hanlin Zhai; Xiangchuan Zhao; Xinxin Li; Yanli Wang; Le Ge; Shengrong Li; Yixin Xu; Zeyu Ming; et al. (Chemical Engineering Journal, 2025)

Activation of Peroxymonosulfate by Magnetic MnFe2O4/MWCNT Toward Rhodamine B Degradation: Efficiency, Mechanism and Influencing Factors - Lijia Zheng; Shoutao Cao; Meng Tang; Ming Ge (Water, Air, & Soil Pollution, 2025)

A Comprehensive Assessment of Water Loss and Driving Forces for the Middle Route of the South-to-North Water Diversion Project from Humanistic Perspective - Jinyu Xiao; Quansheng Ge; Ming Hu; Huijuan Cui (Water Resources Management, 2025)

Microbial degradation of DOC released by the mixed culture of Crassostrea gigas and Undaria pinnatifida - Tian Hu; Jie Su; Kuishuang Shao; Shanshan Dong; Yuyang Xie; Yawen Wei; Hongxia Ming; Tingting Shi; Ge Guo; Jingfeng Fan (Regional Studies in Marine Science, 2024)

Impacts of plastic pollution on soil–plant properties and greenhouse gas emissions in wetlands: A meta-analysis - Wei Zhao; Zhen-Ming Ge; Ke-Hua Zhu; Qing Lyu; Shi-Xian Liu; Hua-Yu Chen; Zeng-Feng Li (Journal of Hazardous Materials, 2024)

m6A RNA methyltransferase METTL16 induces Cr(VI) carcinogenesis and lung cancer development through glutamine biosynthesis and GLUL expression - Yun-Xia Xie; Lin Wang; Zhi-Hao Zhou; Wen-Jing Liu; Wei Wang; Jing-Hua Yang; Ming-Liang He; Jian-Ge Qiu; Bing-Hua Jiang (Journal of Hazardous Materials, 2024)

Understanding the factors influencing high-temperature Daqu from different geographical regions - Zhendong Zhang; Yaolan Meng; Yurong Wang; Qiangchuan Hou; Haibo Zhang; Ming Zhang; Ge Hu; Yingying Zhou; Qifu Pan; Zhuang Guo (Food Bioscience, 2024)

DNA-stable isotope probing and metagenomics reveal Fe(II) oxidation by core microflora in microoxic rhizospheric habitats to mitigate the accumulation of cadmium and phenanthrene in rice - Chen Wu; Sicheng Hang; Feng Li; Yujun Wu; Shengwei Yi; Xingang Liu; Mingjie Chen; Fei Ge; Jiang Tian; Ming Zhang; Dayi Zhang (Environmental Pollution, 2024)

Response strategies of leaf vein traits and stomatal traits of Aegiceras corniculatum to shrimp aquaculture wastewater discharge - Ying-Ying Qin; Ge-Ge Zhu; Ming-Zhong Liang; Hai-Lei Zheng; Jun-Wei Li (Aquatic Ecology, 2024)

Inhibition of human and rat placental 3β-hydroxysteroid dehydrogenases by bisphenol A analogues depends on their hydrophobicity: In silico docking analysis - Shaowei Wang; Han Lu; Yingna Zhai; Yunbing Tang; Ming Su; Huitao Li; Yiyan Wang; Yi Liu; Ren-shan Ge (Chemico-Biological Interactions, 2024)

Coarse particulate air pollution and mortality in a multidrug-resistant tuberculosis cohort - Huiying Feng; Erjia Ge; Nicholas Grubic; Xin Liu; Hui Zhang; Qiang Sun; Xiaolin Wei; Fangjing Zhou; Shanshan Huang; Yuhui Chen; Huixin Guo; Jianwei Li; et al. (Science of The Total Environment, 2024)

Integrated systematic functional screen and fine-mapping decipher the role and genetic regulation of RPS19 in colorectal cancer development - Can Chen; Wenzhuo Wang; Caibo Ning; Zequn Lu; Ming Zhang; Ying Zhu; Jianbo Tian; Haijie Li; Yue Ge; Beifang Yang; Xiaoping Miao (Archives of Toxicology, 2024)

In situ U–Pb dating of garnet, vesuvianite, and scheelite from the Nanyangtian tungsten deposit reveals an Early Cretaceous W mineralization event in Southeast Yunnan, China - Xiao-Yu Zhao; Ming-Guo Deng; Wen-Chang Li; Yan-Wen Tang; Ding-Cai Zhang; Sheng-Kang Han; Wen-Bo Song; Qing-Ge Zhang; Jing-Wei Xu (Gondwana Research, 2024)

AuNPs/DNAzyme/siRNA three-dimensional nanomotor for CEACAM6 RNA detection in cerebrospinal fluid and gene therapy of NSCLC - Fuzhi Shen; Kezhen Ge; Can Yang; Xiao Xu; Shilun Feng; Fenglei Gao; Ming Guan (Chemical Engineering Journal, 2024)

Directional electron transport and strong chloridion repulsion enabled by Hierarchical NiCo2O4/NiCoP heterojunction for efficient seawater oxidation - Yi-Peng Dong; Jiang-Bo Chen; Jie Ying; Yu-Xuan Xiao; Yuan Tian; Ling Shen; Lei Xia; Ge Tian; Si-Ming Wu; Yi Lu; Xiao-Yu Yang (Chemical Engineering Journal, 2024)

The chitinase genes TuCht4 and TuCht10 are indispensable for molting and survival of Tetranychus urticae - Ming Liu; Rongchumu Ge; Lihong Song; Yan Chen; Shuo Yan; Chunya Bu (Insect Biochemistry and Molecular Biology, 2024)

Tree species mixing effects on the radial growth of Pinus massoniana and Castanopsis hystrix: A comparison between even-aged and uneven-aged stands - Renjie Chen; Xiali Guo; Yuxian Ge; Qidong Li; Angang Ming; Huilin Min; Weijun Shen (Forest Ecology and Management, 2024)

Metals/bisulfite system involved generation of 24-sulfonic-25-ene ginsenoside Rg1, a potential quality control marker for sulfur-fumigated ginseng - Hui Liu; Xiao-Qian Wu; Xiang-Ling Qin; Jin-Hao Zhu; Jin-Di Xu; Shan-Shan Zhou; Ming Kong; Hong Shen; Jie-Ge Huo; Song-Lin Li; He Zhu (Food Chemistry, 2024)

Photosynthetic carbon allocation in native and invasive salt marshes undergoing hydrological change - Ya-Lei Li; Li-Na Xie; Shi-Hua Li; Dan Zhang; Zhen-Ming Ge (Science of The Total Environment, 2024)

Hierarchical Nash equilibrium seeking for optimal fault-tolerant formation control of networked MSVs in aggregative games - Yi-Fan Li; Ming-Feng Ge; Qian Chen; Teng-Fei Ding; Zhi-Wei Liu (Ocean Engineering, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

A model coupling ecological and hydrodynamic processes for simulating the biogeomorphology of a coastal salt marsh - Ke-Hua Zhu; Jian Zeng; Zhen-Ming Ge; Yin Zuo; Shi-Hua Li; Lei-Hua Zhao; Yu Han; Hai-Feng Cheng; Pei Xin (Ecological Modelling, 2024)

Tuning multiple enzyme-like activities by metal doping for identification and quantitation of antioxidants in cosmetics - Sheng-Tao Wu; Hui-Qi Su; Kai-Lin Shen; Ying Li; Yi Ge; Xiu-Fang Cheng; Chang-Ming Nie; Cong-Hui Wang; Ying-Wu Lin (Chemical Engineering Journal, 2024)

MIL-88A(Fe)/g-C3N4 composite and its catalytic membrane for tetracycline removal via peroxydisulfate activation: Performance, mechanism and toxicity evaluation - Huayu Wang; Yanhua Cao; Changsheng Guo; Ming Ge (Journal of Environmental Chemical Engineering, 2024)

High efficiency triethylamine gas sensor based on SmVO4 nano octahedron granules - Cheng Yu Xu; Shu Yi Ma; Tian Yuan Dong; Ji Ming Liu; Jin Sha Wei; Hong Tao Jiang; Ping Ni; Ge Ge Fan; Jia Yun Guo (Journal of Environmental Chemical Engineering, 2024)

The metabolic activation of pentachlorophenol to chloranil as a potent inhibitor of human and rat placental 3β-hydroxysteroid dehydrogenases - Weibing Zhang; Ming Su; Hao Lin; Chengshuang Pan; Yunbing Tang; Ren-shan Ge; Qianjin Fei (Toxicology Letters, 2024)

Reducing the accumulation of cadmium and phenanthrene in rice by optimizing planting spacing: Role of low-abundance but core rhizobacterial communities - Chen Wu; Yujun Wu; Feng Li; Xiangxi Ding; Shengwei Yi; Sicheng Hang; Fei Ge; Ming Zhang (Science of The Total Environment, 2024)

The effect of artificial light at night (ALAN) on the characteristics of diapause of Aedes albopictus - Qing Liu; Heng-Duan Zhang; Dan Xing; Jing-Wen Xie; Yu-Tong Du; Ming Wang; Zi-Ge Yin; Nan Jia; Chun-Xiao Li; Teng Zhao; Yu-Ting Jiang; Yan-De Dong; et al. (Science of The Total Environment, 2024)

Growth, nutrient removal, and lipid productivity promotion of Chlorella sorokiniana by phosphate solubilizing bacteria Bacillus megatherium in swine wastewater: Performances and mechanisms - Ya-Ming Ge; Wan-Chuan Xing; Xiu Lu; Shao-Rou Hu; Jun-Zhi Liu; Wei-Feng Xu; Hai-Xiang Cheng; Feng Gao; Qing-Guo Chen (Bioresource Technology, 2024)

Anti-epileptic and Neuroprotective Effects of Ultra-low Dose NADPH Oxidase Inhibitor Dextromethorphan on Kainic Acid-induced Chronic Temporal Lobe Epilepsy in Rats - Jing-Jing Yang; Ying-Xin Liu; Yan-Fang Wang; Bi-Ying Ge; Ying Wang; Qing-Shan Wang; Sheng Li; Jian-Jie Zhang; Ling-Ling Jin; Jau-Shyong Hong; Sheng-Ming Yin; Jie Zhao (Neuroscience Bulletin, 2024)

Demethoxylation of curcumin enhances its inhibition on human and rat 17β-hydroxysteroid dehydrogenase 3: QSAR structure-activity relationship and in silico docking analysis - Zhongyao Ji; Jianmin Sang; Hong Wang; Miaomiao Xia; Ting Hao; Liping Chen; Han Lu; Shaowei Wang; Ming Yao; Linxi Li; Ren-shan Ge (Food and Chemical Toxicology, 2024)

Phthalate drives splenic inflammatory response via activating HSP60/TLR4/NLRP3 signaling axis-dependent pyroptosis - Xin-Ran Ge; Yi Zhao; Hao-Ran Ren; Fu-Wei Jiang; Shuo Liu; Ming Lou; Yi-Feng Huang; Ming-Shan Chen; Jia-Xin Wang; Jin-Long Li (Environmental Pollution, 2024)

Does livestock-Manure-Derived Biochar Suitable for the Stabilization of Cadmium and Zinc in Contaminated Soil? - Zhiqiang Jiao; Shiji Ge; Ming Chen; Paramsothy Jeyakumar; Hailong Wang; Xiaojun Xu; Yangyang Wang (Bulletin of Environmental Contamination and Toxicology, 2024)

The Complete Genomic Sequence of Microbial Transglutaminase Producer, Streptomyces mobaraensis DSM40587 - Xi-long Feng; Rui-qi Zhang; Wei-ge Dong; Zhen-xin Wang; Jun-jie Xiao; Jing Wei; Jin-ming Gao; Jianzhao Qi (Biochemical Genetics, 2024)

Ionic liquid microwave-assisted hydrodistillation extraction of Angelica sinensis essential oil and its own anti-inflammatory and antioxidant activities - Taotao Li; Huanxian Shi; Wenfei Wang; Jia Li; Tiantian Tang; Yujiao Wang; Ding Liu; Kai Yang; Xuan Wang; Jie Wang; Ning Xia; Jinhui Wang; et al. (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

OsGEX3 affects anther development and improves osmotic stress tolerance in rice - Han Bao; Yuchao Cui; Li Ge; Yan Li; Xiaorong Xu; Ming Tang; Yin Yi; Liang Chen (Planta, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

A Study on the Assessment and Integration of Multi-Source Evapotranspiration Products over the Tibetan Plateau - Ming Cheng; Lei Zhong; Yaoming Ma; Han Ma; Yaoxin Chang; Peizhen Li; Meilin Cheng; Xian Wang; Nan Ge (Advances in Atmospheric Sciences, 2024)

Finite-time multi-surrounding control of networked marine surface vehicles: A three-layer-hierarchical approach - Kai-Lun Huang; Chang-Duo Liang; Ming-Feng Ge; Xionghua Liu; Qian Chen; Wuqiong Cai (Ocean Engineering, 2024)

Chalcones from plants cause toxicity by inhibiting human and rat 11β-hydroxysteroid dehydrogenase 2: 3D-quantitative structure-activity relationship (3D-QSAR) and in silico docking analysis - Hang Lin; Ming Su; Chao Wen; Yunbing Tang; Huitao Li; Yandan Wu; Ren-shan Ge; Xing-wang Li; Han Lin (Food and Chemical Toxicology, 2024)

Interactions between soil bacterial communities, assembly processes and microbial functions along the elevational gradient - Donghui Zhao; Congcong Shen; Zhi-Ming Zhang; Jichen Wang; Li-Mei Zhang; Baodong Chen; Guo-Xin Sun; Yuan Ge (CATENA, 2024)

TET1 Regulates Proliferation of Mouse Skin-Derived Stem Cells In Vitro - Tian Qiao; Li Li; Ming-Xin Zang; Yi-Nuo Jiang; Sha-Sha Wang; Chun-Xiao Li; Xin-Xiang Xie; Geng Zhang; Ying Zhang; Wei Ge; Wei Shen; Shun-Feng Cheng (Stem Cell Reviews and Reports, 2024)

IGF2BP1 facilitates non-small cell lung cancer progression by regulating the KIF2A-mediated Wnt/β-catenin pathway - Ming Sun; Ling Wang; Lei Ge; Daojun Xu; Renquan Zhang (Functional & Integrative Genomics, 2024)

Circ_0091579 Knockdown Inhibited HCC Proliferation and Glutamine Metabolism Through miR-1270/YAP1 Axis - Ming Liu; Bing Guo; Ge Zhang; Huanpeng Qi (Biochemical Genetics, 2024)

Morphological and phylogenetic analyses reveal a new species of Anthracophyllum (Omphalotaceae, Agaricales) in Zhejiang Province, China - Wen-Juan Yang; Miao Xu; Jing Zhang; Fan Zhou; Zhi-Fang Le; Wen-Jun Tong; Hai-Yan Song; Zhuo-Han Jin; Qiu-Ge Cheng; Jian-Ping Zhou; Yang Gao; Zhi-Jun Zhai; et al. (Archives of Microbiology, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Cobalt-loaded carbon nanofibers as magnetic catalyst for tetracycline degradation through peroxydisulfate activation: Non-radical dominated mechanism - Yifan Wang; Xiaoxuan Kang; Yuting Li; Ruyi Li; Chang Wu; Luyao Wang; Chongqing Wang; Tao Yang; Ming Ge; Zhangxing He (Journal of Water Process Engineering, 2024)

Synthesis of defective Ni-Mn layered double hydroxides nanosheets via alkali-assisted Mo doping for urea electro-oxidation - Ming Yang; Wanyu Ge; Zirui Liu; Qiang Yue; Jun Zhang; Yanping Lv; Hao Wu (Fuel, 2024)

Robust iron-doped manganese oxide nanoparticles from facile fabrication to photo-catalytic degradation application of binary dyes mixture - Shizhong Zhang; Sohail Khan; Falak Naz; Ayesha Noman; Arif Nawaz; Sajid Ali; Khalid Saeed; Nisar Ali; Ming Ge (Environmental Research, 2024)

Nature-based solutions to mitigate early marsh-edge erosion in a coastal wetland - Ke Zhou; Shi-Xian Liu; Hai-Feng Cheng; Ke-Hua Zhu; Wei Zhang; Qing Lyu; Hua-Yu Chen; Pei Xin; Zhen-Ming Ge (Ecological Engineering, 2024)

A wearable self-powered microneedle system based on conductive drugs for infected wound healing: A new electrical stimulation delivery strategy - Shanguo Zhang; Tianyi Jiang; Fang Han; Liangyu Cao; Ming Li; Zhenyou Ge; Haoxiu Sun; Hao Wu; Wenlong Wu; Nannan Zhou; Muhammad Luqman Akhtar; Hongyuan Jiang (Chemical Engineering Journal, 2024)

Unraveling the potential-dependent structure evolution in CuO for electrocatalytic biomass valorization - Ye Wang; Ming Xu; Xi Wang; Ruixiang Ge; Yu-Quan Zhu; An-Zhen Li; Hua Zhou; Fengen Chen; Lirong Zheng; Haohong Duan (Science Bulletin, 2023)

Insights into metal/carbon materials activation of persulfate from a structure–property perspective: Performances, tunable reaction pathways and toxicity - Hao Ge; Min Cheng; DanLian Huang; Ming Yan; Zhen Wei; Gaoxia Zhang; Li Du; Guangfu Wang; Hongda Liu; Shaoheng Liu; Yongxi Chen (Chemical Engineering Journal, 2023)

CDC20 promotes radioresistance of prostate cancer by activating Twist1 expression - Chuanlai Yang; Yuegang Ge; Yachen Zang; Ming Xu; Lu Jin; Yang Wang; Xinyu Xu; Boxin Xue; Zhiwei Wang; Lixia Wang (Apoptosis, 2023)

Dike risk evaluation incorporating the contribution of coastal wetlands: A case study on Chongming Island, China - Wei Zhang; Jian Zeng; Zhen-Ming Ge; Peng Yun; Ke-Hua Zhu; Ke Zhou; Shi-Xian Liu; Qing Lyu; Hua-Yu Chen (Ocean & Coastal Management, 2023)

Dual roles of the Arabidopsis PEAT complex in histone H2A deubiquitination and H4K5 acetylation - Si-Yao Zheng; Bin-Bin Guan; Dan-Yang Yuan; Qiang-Qiang Zhao; Weiran Ge; Lian-Mei Tan; Shan-Shan Chen; Lin Li; She Chen; Rui-Ming Xu; Xin-Jian He (Molecular Plant, 2023)

Effects of plastic contamination on carbon fluxes in a subtropical coastal wetland of East China - Wei Zhao; Ke-Hua Zhu; Zhen-Ming Ge; Qing Lv; Shi-Xian Liu; Wei Zhang; Pei Xin (Journal of Environmental Management, 2023)

Prussian blue analogues-derived zero valent iron to efficiently activate peroxymonosulfate for phenol degradation triggered via reactive oxygen species and high-valent iron-oxo complexes - Tong Wei; Xin-Sheng Zhu; Qi-Xue Wang; Ke-Ke Xu; Fu-Kai Tang; Ming-Zhu Zhang; Shi-Wen Lv; Feng Ge (Environmental Research, 2023)

Demethylation-Driven ligase chain reaction for simultaneously sensitive detection of m6A demethylase FTO and m1A demethylase ALKBH3 in breast cancer at Single-Molecule level - Ming-hao Liu; Qian Zhang; Wan-tong Yu; Jian-Ge Qiu; Hui-min Yuan; Chuan-rui Wang; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Chemical Engineering Journal, 2023)

Advances and Applications of Brain Organoids - Yang Li; Peng-Ming Zeng; Jian Wu; Zhen-Ge Luo (Neuroscience Bulletin, 2023)
Understanding the fundamental processes of human brain development and diseases is of great importance for our health. However, existing research models such as non-human primate and mouse models remain limited due to their developmental discrepancies compared with humans. Over the past years, an emerging model, the “brain organoid” integrated from human pluripotent stem cells, has been developed to mimic developmental processes of the human brain and disease-associated phenotypes to some extent, making it possible to better understand the complex structures and functions of the human brain. In this review, we summarize recent advances in brain organoid technologies and their applications in brain development and diseases, including neurodevelopmental, neurodegenerative, psychiatric diseases, and brain tumors. Finally, we also discuss current limitations and the potential of brain organoids.

An approach for multi-objective optimization based on preliminary PSA and its applications for fusion reactors - Ming Sun; Jie Yu; Taosheng Li; Daochuan Ge (Annals of Nuclear Energy, 2023)

Protective effects of maternal administration of total saponins of Codonopsis pilosula in the mice offspring following diarrhea: role of immune function, antioxidant function, and intestinal inflammatory injury - Jiali Li; Yiming Sun; Naixi Yang; Haolin Zhang; Yihan Hu; Haibin Wang; Ruili Zhang; Ming Ge (Environmental Science and Pollution Research, 2023)

Thyroid disrupting effects of multiple metals exposure: Comprehensive investigation from the thyroid parenchyma to hormonal function in a prospective cohort study - Ang Li; Quan Zhou; Yayuan Mei; Jiaxin Zhao; Meiduo Zhao; Jing Xu; Xiaoyu Ge; Yanbing Li; Kai Li; Ming Yang; Qun Xu (Journal of Hazardous Materials, 2023)

Co-transformation of HMs-PAHs in rhizosphere soils and adaptive responses of rhizobacteria during whole growth period of rice (Oryza sativa L.) - Shengwei Yi; Feng Li; Chen Wu; Fei Ge; Chuang Feng; Ming Zhang; Yun Liu; Hainan Lu (Journal of Environmental Sciences, 2023)

Experimental study on Diels-Alder addition of conjugated dienes directly from cracking C5 fraction by continuous micro-channel reactors - Zehao Jing; Tingting Ge; Hui Guo; Yuchao Li; Zhou Li; Cuncun Zuo; Ming Wang; Haofei Huang; Lin Guo; Guangjun Cui (Fuel, 2023)

Beijing Children’s Hospital guidelines on the design and conduction of the first standardized database for medulloblastoma - Wei Yang; Wenping Ma; Jiansong Huang; Yingjie Cai; Xiaojiao Peng; Fengmao Zhao; Di Zhang; Zhewei Zou; Hailang Sun; Xiang Qi; Ming Ge (Metabolic Brain Disease, 2023)

Development of a N6-methyladenosine-directed single quantum dot-based biosensor for sensitive detection of METTL3/14 complex activity in breast cancer tissues - Ming-hao Liu; Wan-tong Yu; Ning-ning Zhao; Jian-Ge Qiu; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Analytica Chimica Acta, 2023)

Permeability decides the effect of antibiotics on sedimentary nitrogen removal in Jiulong River Estuary - Ru Wan; Lianghao Ge; Bin Chen; Jin-Ming Tang; Ehui Tan; Wenbin Zou; Li Tian; Meng Li; Zongbao Liu; Lijun Hou; Guoyu Yin; Shuh-Ji Kao (Water Research, 2023)

Impacts of land-use change on carbon dynamics in China's coastal wetlands - Li-Shan Tan; Zhen-Ming Ge; Shi-Hua Li; Ke Zhou; Derrick Y.F. Lai; Stijn Temmerman; Zhi-Jun Dai (Science of The Total Environment, 2023)

Trichlorfon blocks androgen synthesis and metabolism in rat immature Leydig cells - Huan Chen; Yaoyao Dong; Huitao Li; Zhili Chen; Ming Su; Qiqi Zhu; Ren-Shan Ge; Xinjun Miao (Reproductive Toxicology, 2023)

Distributed optimization of networked marine surface vehicles: A fixed-time estimator-based approach - Qian Chen; Ming-Feng Ge; Chang-Duo Liang; Zhi-Wei Gu; Jie Liu (Ocean Engineering, 2023)

Microplastics affect activity and spatial distribution of C, N, and P hydrolases in rice rhizosphere - Yaoyao Tong; Jina Ding; Mouliang Xiao; Muhammad Shahbaz; Zhenke Zhu; Ming Chen; Yakov Kuzyakov; Yangwu Deng; Jianping Chen; Tida Ge (Soil Ecology Letters, 2023)

Rotifer distribution patterns in relation to dissolved organic matter in the middle reaches of Huai River Basin during the dry season - Leilei Luan; Liangmin Gao; Xudong Chen; Juan Ge; Ming Mu; Xiaoqing Chen; Xinglan Zhao; Zhen Zhang; Haiqiang Zhang (Environmental Science and Pollution Research, 2023)

Hydrochemical characteristics of groundwater in a plain river network region: Establishing linkages between source and water quality variables - Ning Ma; Li Gao; Zhengkui Ge; Ming Li (Chemosphere, 2023)

A taphonomic clock based on the coral grain size of beach sediments from the Yongle Atoll, South China Sea - Yali Li; Xinqing Zou; Ming Tan; Chendong Ge; Meng Tang; Teng Wang; Xuefeng Wang (Geomorphology, 2023)

Molecularly imprinted polymers based on calcined rape pollen and deep eutectic solvents for efficient sinapic acid extraction from rapeseed meal extract - Yanhua Sun; Yange Zhang; Yujiao Hou; Hui Gong; Yifei Pang; Xiaoxiao Ge; Ming Li (Food Chemistry, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Enhancing thermoelectric performance of n-type Bi2Te2.7Se0.3 through the incorporation of MnSb2Se4 nanoinclusions - Tao Chen; Xiaoying Qin; Hongwei Ming; Xuemei Zhang; Ziyuan Wang; Shuhuan Yang; Yongsheng Zhang; Zhenhua Ge; Hongxing Xin; Di Li; Jian Zhang (Chemical Engineering Journal, 2023)

Facile preparation of a novel iminodisuccinate modified chitin and its excellent properties as a silver bioadsorbent and antibacterial agent - Ya-Ming Ge; Yong Zhang; Jia-Shun Yang; Wang-Yang Ye; Hui-Min Gao; Jun-Zhi Liu; Qi-Bei Bao; Wei Jiang (Carbohydrate Polymers, 2023)

Exogenous hydrogen sulphide alleviates nodule senescence in Glycine max-Sinorhizobium fredii symbiotic system - Juan Chen; Wu-Yu Liu; Xin Zhang; Qing Pan; Feng-Shuya Wang; Shi-Ming Wen; Jian-Hua Zhang; Ge-Hong Wei (Plant and Soil, 2023)

Urban vitality assessment at the neighborhood scale with geo-data: A review toward implementation - Sheng Liu; Jian Ge; Xinyue Ye; Chao Wu; Ming Bai (Journal of Geographical Sciences, 2023)

The combined effect of seawater salinity and duration on the survival and growth of eelgrass Zostera marina - Yan-Hao Zhang; Jian-Du Li; Wen-Jie Yan; Fan-Shu Luo; Li Wang; Li-Ming Zuo; Jun-Ge Xu; Wen-Tao Li; Pei-Dong Zhang (Aquatic Botany, 2023)

Magnetic MnFe2O4 nanoparticles anchored on sludge-derived biochar in activating peroxydisulfate for levofloxacin degradation: Mechanism, degradation pathways and cost analysis - Xiaoyan Meng; Tingting Song; Chao Zhang; Huayu Wang; Ming Ge; Changsheng Guo (Journal of Environmental Chemical Engineering, 2023)

Active pollination in a functionally dioecious Ficus species: An interplay between pollinator behaviour and floral morphology - Bai-Ge Miao; Ming-Xin Liu; Bo Wang; Yan-Qiong Peng; Annick Lesne; Finn Kjellberg; K．Charlotte Jandér (Flora, 2023)

Au/SiNCA-based SERS analysis coupled with machine learning for the early-stage diagnosis of cisplatin-induced liver injury - Shengjie Ge; Gaoyang Chen; Dawei Cao; Hechuan Lin; Ziyang Liu; Meng Yu; Shiyi Wang; Zhigang Wang; Ming Zhou (Analytica Chimica Acta, 2023)

Sunlight-mediated CaO2 inactivation of pathogen indicator organisms in surface water system: Roles of reactive species, characterization of pathogen inactivation - Shuwen Zhang; Ming Zheng; Ge Yang; Ting Zhang; Jason T. Magnuson; Honghong Chen; Chunmiao Zheng; Wenhui Qiu (Water Research, 2023)

Structural, in vitro digestion, and fermentation characteristics of lotus leaf flavonoids - Jicai Feng; Jian Wang; Tingting Bu; Zhiwei Ge; Kai Yang; Peilong Sun; Liehong Wu; Ming Cai (Food Chemistry, 2023)

Mechanical properties of auxetic circular and square tubes filled with aluminum foam - Ru Yuan Huo; Dong Han; Yi Zhang; Wei Jiang; Le Yang Fan; Xin Wei Peng; Ge Chen Jie Shi; Ming Hao Chu; Xiang Yu Zhang; Yi Min Xie; Xin Ren (Engineering Structures, 2023)

Effective Removal of Aqueous Cu(II) Pollution by a Novel Readily Prepared Porous Biomaterial Using Crab Shell Wastes - Ya-Ming Ge; Liang Zhang; Yong Zhang; Jia-Shun Yang; Hui-Min Gao; Shi-Jie Li; Jun-Zhi Liu (Water, Air, & Soil Pollution, 2023)

Efficient coupling of sulfadiazine removal with microalgae lipid production in a membrane photobioreactor - Feng Gao; Jin-Long Zhou; Yu-Ru Zhang; Ashiwin Vadiveloo; Qing-Guo Chen; Jun-Zhi Liu; Qiao Yang; Ya-Ming Ge (Chemosphere, 2023)

The essentiality of dietary myo-inositol to oriental river prawn (Macrobrachium nipponense): Evidence in growth performance, lipid metabolism and mitochondrial function - Ming-Yang Liu; Miao Sun; Ling Zhang; Ya-Ping Ge; Bo Liu; Xiang-Fei Li (Aquaculture, 2023)

Transition of source/sink processes and fate of ammonium in groundwater along with redox gradients - Li-Li Han; Helin Wang; Lianghao Ge; Min Nina Xu; Jin-Ming Tang; Li Luo; Ping Li; Shuh-Ji Kao (Water Research, 2023)

Adaptive reinforcement learning fault-tolerant control for AUVs With thruster faults based on the integral extended state observer - Zhifu Li; Ming Wang; Ge Ma; Tao Zou (Ocean Engineering, 2023)

Morphology evolution regulation of dual-doped S, Fe-NiMoO4 microrods based on precipitation-dissolution equilibrium for oxygen evolution - Meng-Xuan Li; Bo Xiao; Zi-Yi Zhao; Yu Ma; Ya-Nan Zhou; Xin-Yu Zhang; Feng-Ge Wang; Yong-Ming Chai; Bin Dong (Fuel, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Improving the genome and proteome annotations of the marine model diatom Thalassiosira pseudonana using a proteogenomics strategy - Xiao-Huang Chen; Ming-Kun Yang; Yuan-Yuan Li; Zhang-Xian Xie; Shu-Feng Zhang; Mats Töpel; Shady A. Amin; Lin Lin; Feng Ge; Da-Zhi Wang (Marine Life Science & Technology, 2023)
Diatoms are unicellular eukaryotic phytoplankton that account for approximately 20% of global carbon fixation and 40% of marine primary productivity; thus, they are essential for global carbon biogeochemical cycling and climate. The availability of ten diatom genome sequences has facilitated evolutionary, biological and ecological research over the past decade; however, a complimentary map of the diatom proteome with direct measurements of proteins and peptides is still lacking. Here, we present a proteome map of the model marine diatom Thalassiosira pseudonana using high-resolution mass spectrometry combined with a proteogenomic strategy. In-depth proteomic profiling of three different growth phases and three nutrient-deficient samples identified 9526 proteins, accounting for ~ 81% of the predicted protein-coding genes. Proteogenomic analysis identified 1235 novel genes, 975 revised genes, 104 splice variants and 234 single amino acid variants. Furthermore, our quantitative proteomic analysis experimentally demonstrated that a considerable number of novel genes were differentially translated under different nutrient conditions. These findings substantially improve the genome annotation of T. pseudonana and provide insights into new biological functions of diatoms. This relatively comprehensive diatom proteome catalog will complement available diatom genome and transcriptome data to advance biological and ecological research of marine diatoms.

Recent advances in persulfate activation by magnetic ferrite-carbon composites for organic contaminants degradation: Role of carbon materials and environmental application - Tingting Song; Xiaoxuan Kang; Changsheng Guo; Zhangxing He; Ming Ge (Journal of Environmental Chemical Engineering, 2023)

Mn-induced strengthening hybridization effect of Co–O bond for stable oxygen evolution in acidic media - Ruo-Yao Fan; Hui-Ying Zhao; Yi-Nuo Zhen; Feng-Ge Wang; Han Hu; Yong-Ming Chai; Bin Dong (Fuel, 2023)

A Method for Reducing Ocean Wave-Induced Magnetic Noises in Shallow-Water MT Data Using a Complex Adaptive Filter - Yunju Wu; Ming Luo; Yuguo Li; Jiaqi Ge; Lindong Pan (Journal of Ocean University of China, 2023)

Pore reconstruction mechanism of wheat straw-templated Li4SiO4 pellets for CO2 capture - Yingchao Hu; Hongyuan Lu; Zhe Lv; Ming Zhang; Ge Yu (Science of The Total Environment, 2023)

The distinct resistance mechanisms of cyanobacteria and green algae to sulfamethoxazole and its implications for environmental risk assessment - Yibo Zhang; Ming Li; Fang Chang; Malan Yi; Hongmei Ge; Jie Fu; Chenyuan Dang (Science of The Total Environment, 2023)

Predefined-time formation control of NASVs with fully discontinuous communication: A novel hierarchical event-triggered scheme - Ya-Qi Yang; Ming-Feng Ge; Chang-Duo Liang; Kun-Ting Xu; Leimin Wang (Ocean Engineering, 2023)

Effects of waterlogging and elevated salinity on the allocation of photosynthetic carbon in estuarine tidal marsh: a mesocosm experiment - Ya-Lei Li; Zhen-Ming Ge; Li-Na Xie; Shi-Hua Li; Li-Shan Tan; Kasper Hancke (Plant and Soil, 2023)

ESO-based event-triggered attitude control of spacecraft with unknown actuator faults - Chun-Yang Kong; Dang-Jun Zhao; Ming-Zhe Dai; Bu-Ge Liang (Advances in Space Research, 2023)

Transplantation of Nasal Olfactory Mucosa Mesenchymal Stem Cells Benefits Alzheimer’s Disease - Chun-Gu Hong; Meng-Lu Chen; Ran Duan; Xin Wang; Zhi-Lin Pang; Li-Te Ge; Ming Lu; Hui Xie; Zheng-Zhao Liu (Molecular Neurobiology, 2022)

Comprehensive comparison of the prognostic value of systemic inflammation biomarkers for cancer cachexia: a multicenter prospective study - Hailun Xie; Guotian Ruan; Lishuang Wei; Heyang Zhang; Yizhong Ge; Qi Zhang; Shiqi Lin; Mengmeng Song; Xi Zhang; Xiaoyue Liu; Ming Yang; Meng Tang; et al. (Inflammation Research, 2022)

Facile synthesis of magnetic ZnFe2O4/AC composite to activate peroxydisulfate for dye degradation under visible light irradiation - Tingting Song; Quanbao He; Xiaoyan Meng; Zhangxing He; Ming Ge (Environmental Science and Pollution Research, 2022)

Protective Effects of Astilbin Against Cadmium-Induced Apoptosis in Chicken Kidneys via Endoplasmic Reticulum Stress Signaling Pathway - Xiuyu Li; Ming Ge; Weifeng Zhu; Panpan Wang; Jiangfeng Wang; Tiange Tai; Yuxi Wang; Jianxu Sun; Guangliang Shi (Biological Trace Element Research, 2022)

Pathological Networks Involving Dysmorphic Neurons in Type II Focal Cortical Dysplasia - Yijie Shao; Qianqian Ge; Jiachao Yang; Mi Wang; Yu Zhou; Jin-Xin Guo; Mengyue Zhu; Jiachen Shi; Yiqi Hu; Li Shen; Zhong Chen; Xiao-Ming Li; et al. (Neuroscience Bulletin, 2022)

Spatial variation in bacterial community and dissolved organic matter composition in groundwater near a eutrophic lake - Ning Ma; Li Gao; Yan Zhang; Zhengkui Ge; En Hu; Baozhu Pan; Jian Wang; Ming Li (Aquatic Ecology, 2022)

Genome characterization and comparative analysis among three swimming crab species - Ming Liu; Shanshan Ge; Shivish Bhandari; Chunlei Fan; Yu Jiao; Chunlei Gai; Youhong Wang; Hongjun Liu (Frontiers in Marine Science, 2022)
In this study we sequenced the genomes of three economically important swimming crabs Portunus trituberculatus, Charybdis japonica , and Callinectes sapidus using the next-generation sequencing approach and made a basic assembly. The genomes of the three species are characterized with high heterozygosity (>1.2%) and high repeat content (>50%). Genome comparative analysis revealed 40 long conserved fragments (>5,000 bp) among the three species, most of them are involved in cardiac-related biological process. Relative higher genome similarity was found between P. trituberculatus and C. japonica that are belong to different subfamilies, compared to that between P. trituberculatus and C. sapidus which are from the same subfamily. It is inconsistent with their phylogenetic evolutionary trees inferred from previous mitochondrial DNA coding fragments and a conserved ANK2 protein fragment from this study. We speculated that the high genome similarity between P. trituberculatus and C. japonica might be attributed to their same inhabit range in which the genome is subject to the same environment selection, and the inconsistence between genome similarity and phylogenetic relationship is caused by the different evolutionary rates of coding DNA and non-coding DNA under environment selection.

Male Predisposition in Cerebellar Mutism Syndrome: a Cohort Study - Wei Yang; Ming Ge; Kaiyi Zhu; Jiashu Chen; Ping Yang; Yingjie Cai; XiaoJiao Peng; Jia Wang; Hailang Sun; Yuanqi Ji; Fengmao Zhao; Hong Zhang (The Cerebellum, 2022)

Statin therapy protects against abdominal aortic aneurysms by inducing the accumulation of regulatory T cells in ApoE−/− mice - Linlin Meng; Yue Lu; Xinlu Wang; Wenhai Sui; Xiao Ge; Ming Zhong; Xiao Meng; Yun Zhang (Journal of Molecular Medicine, 2022)

Reduction the contamination of patulin during the brewing of apple cider and its characteristics - Zhouli Wang; Leran Wang; Qiaoying Ming; Tianli Yue; Qian Ge; Yahong Yuan; Zhenpeng Gao; Rui Cai (Food Additives & Contaminants: Part A, 2022)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

Alexandriicola marinus gen. nov., sp. nov., a new member of the family Rhodobacteraceae isolated from marine phycosphere - Wen-Zhuo Zhu; Hui-Min Gao; Ya-Ming Ge; Jun Dai; Xi Yang; Xiao-Ling Zhang; Qiao Yang (Antonie van Leeuwenhoek, 2022)

Holocene hydroclimate changes on the north‐eastern Tibetan Plateau inferred from geochemical records in Lake Gyaring - Dongliang Ning; Qingfeng Jiang; Ming Ji; Yuchen Xu; Xiang Kuai; Ying Ge; Wenwei Zhao (Journal of Quaternary Science, 2022)
The north‐eastern Tibetan Plateau (TP) is an ideal region for understanding the interaction between the Asian Summer Monsoon (ASM) and the Westerlies. Here we present a high‐resolution elemental record from Lake Gyaring in the source region of the Yellow River to investigate the paleo‐hydroclimate changes over the past ~10 ka. Our results show that lithogenic elements (Ti, Rb, Mn, Ti, Zn and Ni) increased while carbonate‐related elements (Ca, Sr and Mg) decreased up the core sediments, indicating that the effective moisture on the north‐eastern TP has steadily increased throughout the Holocene. This inference is also supported by the gradual augmentation and diminution of Rb/Sr and Ca/(Ti + Fe + Al) ratios, respectively. The persistent wetting trend on the north‐eastern TP inferred from our study disagrees with the Holocene pattern of the ASM but corresponds well with that of the Westerlies. This implies that the strengthening Westerlies since the Holocene might have played a more important role than monsoon circulation in controlling the hydroclimate changes on the north‐eastern TP. However, the significant increase in the mid‐Holocene might be related to the combined effects of the strengthened ASM and Westerlies. Ultimately, Northern Hemisphere solar insolation and the substantial remnant of ice sheets might have controlled Holocene moisture availability on the north‐eastern TP through their influence on the intensity of the Westerlies and ASM as well as Atlantic Ocean sea surface temperatures.

GIS-based spatial prediction of landslide using road factors and random forest for Sichuan-Tibet Highway - Cheng-ming Ye; Rui-long Wei; Yong-gang Ge; Yao Li; José Marcato Junior; Jonathan Li (Journal of Mountain Science, 2022)

Astragalus Polysaccharide Protects Against Cadmium-Induced Autophagy Injury Through Reactive Oxygen Species (ROS) Pathway in Chicken Embryo Fibroblast - Xudong Shen; Zequn Tang; Yu Bai; Meishuo Wan; Miao Yu; Jingyi Chen; Guangxing Li; Ruili Zhang; Ming Ge (Biological Trace Element Research, 2022)

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

Evaluation of four artificial diets on demography parameters of Neoseiulus barkeri - Ya-Ying Li; Jin-Ge Yuan; Ming-Xiu Liu; Zi-Hui Zhang; Hai-Wei Zhou; Huai Liu (BioControl, 2021)

Gephyromycinifex aptenodytis gen. nov., sp. nov., isolated from gut of Antarctic emperor penguin Aptenodytes forsteri - Wen-Zhuo Zhu; Ya-Ming Ge; Hui-Min Gao; Jun Dai; Xiao-Ling Zhang; Qiao Yang (Antonie van Leeuwenhoek, 2021)

Growth, serum biochemical parameters, salinity tolerance and antioxidant enzyme activity of rainbow trout (Oncorhynchus mykiss) in response to dietary taurine levels - Ming Huang; Xiaogang Yang; Yangen Zhou; Jian Ge; D. Allen Davis; Yunwei Dong; Qinfeng Gao; Shuanglin Dong (Marine Life Science & Technology, 2021)

Functional homoeologous alleles of CONSTANS contribute to seasonal crop type in rapeseed - Qingdong Jin; Shuai Yin; Ge Li; Tao Guo; Ming Wan; Haitao Li; Juanjuan Li; Xianhong Ge; Graham J. King; Zaiyun Li; Jing Wang; Guangsheng Zhou (Theoretical and Applied Genetics, 2021)

A methyl esterase 1 (PvMES1) promotes the salicylic acid pathway and enhances Fusarium wilt resistance in common beans - Renfeng Xue; Ming Feng; Jian Chen; Weide Ge; Matthew W. Blair (Theoretical and Applied Genetics, 2021)

Effects of different temperatures on seawater acclimation in rainbow trout Oncorhynchus mykiss: osmoregulation and branchial phospholipid fatty acid composition - Jian Ge; Ming Huang; Yangen Zhou; Chengyue Liu; Cui Han; Qinfeng Gao; Yunwei Dong; Shuanglin Dong (Journal of Comparative Physiology B, 2021)

Sulfitobacter alexandrii sp. nov., a new microalgae growth-promoting bacterium with exopolysaccharides bioflocculanting potential isolated from marine phycosphere - Qiao Yang; Ya-ming Ge; Nurhezreen Md Iqbal; Xi Yang; Xiao-ling Zhang (Antonie van Leeuwenhoek, 2021)

Altered structural and functional connectivity in CSF1R-related leukoencephalopathy - Fei-Xia Zhan; Ze-Yu Zhu; Qing Liu; Hai-Yan Zhou; Xing-Hua Luan; Xiao-Jun Huang; Xiao-Li Liu; Wo-Tu Tian; Shi-Ge Wang; Xiao-Xuan Song; Guang Chen; Ming-Liang Zhao; et al. (Brain Imaging and Behavior, 2021)

Sphingopyxis microcysteis sp. nov., a novel bioactive exopolysaccharides-bearing Sphingomonadaceae isolated from the Microcystis phycosphere - Xiao-ling Zhang; Gui-xian Li; Ya-ming Ge; Nurhezreen Md Iqbal; Xi Yang; Zhen-dong Cui; Qiao Yang (Antonie van Leeuwenhoek, 2021)

Effects of seawater acclimation at constant and diel cyclic temperatures on growth, osmoregulation and branchial phospholipid fatty acid composition in rainbow trout Oncorhynchus mykiss - Jian Ge; Ming Huang; Yangen Zhou; Qianlong Deng; Rongxin Liu; Qinfeng Gao; Yunwei Dong; Shuanglin Dong (Journal of Comparative Physiology B, 2021)

Fatty Acid Composition and Digestive Enzyme Activities of Rainbow Trout in Response to Dietary Docosahexaenoic Acid (DHA) and Eicosapentaenoic Acid (EPA) During Salinity Acclimation - Ming Huang; Yangen Zhou; Jian Ge; Thorleifur Agustsson; Li Li; Qinfeng Gao; Shuanglin Dong (Journal of Ocean University of China, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Protectin DX ameliorates inflammation in sepsis-induced acute lung injury through mediating PPARγ/NF-κB pathway - Haifa Xia; Yangyang Ge; Fuquan Wang; Yu Ming; Zhouyang Wu; Jingxu Wang; Shujun Sun; Shiqian Huang; Ming Chen; Weimin Xiao; Shanglong Yao (Immunologic Research, 2020)

Shelf-life Prediction of Chilled Penaeus vannamei Using Grey Relational Analysis and Support Vector Regression - Xingxing Huang; Ming Chen; Wenjuan Wang; Yan Ge; Jing Xie (Journal of Aquatic Food Product Technology, 2020)

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

Deep RNA-seq analysis reveals key responding aspects of wild banana relative resistance to Fusarium oxysporum f. sp. cubense tropical race 4 - Wei-Ming Li; Miguel Dita; Mathieu Rouard; Wei Wu; Nicolas Roux; Jiang-Hui Xie; Xue-Jun Ge (Functional & Integrative Genomics, 2020)

Possible aerosol transmission of COVID-19 and special precautions in dentistry - Zi-yu Ge; Lu-ming Yang; Jia-jia Xia; Xiao-hui Fu; Yan-zhen Zhang (Journal of Zhejiang University-SCIENCE B, 2020)

Bifidobacterium bifidum TMC3115 Can Characteristically Influence Glucose and Lipid Profile and Intestinal Microbiota in the Middle-Aged and Elderly - Ke Wang; Xiaohong Yu; Yi Li; Yun Guo; Lin Ge; Fangfang Pu; Xinying Ma; Wenjing Cui; Francesco Marrota; Fang He; Ming Li (Probiotics and Antimicrobial Proteins, 2019)

Correlation between shear strength and soil physicochemical properties of different weathering profiles of the non-eroded and collapsing gully soils in southern China - Bifei Huang; Ming Qiu; Jinshi Lin; Jialin Chen; Fangshi Jiang; Ming-kuang Wang; Hongli Ge; Yanhe Huang (Journal of Soils and Sediments, 2019)

Effects of Fungal Polysaccharide on Oxidative Damage and TLR4 Pathway to the Central Immune Organs in Cadmium Intoxication in Chickens - Ruyue Li; Linan Zhang; Zequn Tang; Tianqi Li; Guangxing Li; Ruili Zhang; Ming Ge (Biological Trace Element Research, 2019)

Nitrous oxide emission rate in response to plant, soil and microbial properties in marshes impacted by alien Spartina alterniflora - Chongbang Zhang; Wenli Liu; Ming Guan; Jiang Wang; Xiaocui Pan; Ying Ge; Jie Chang (Biologia, 2019)

Clinical and molecular characteristics of thirty NF1 variants in Chinese patients with neurofibromatosis type 1 - Wen Wang; Weibing Qin; Hongsong Ge; Xiangsheng Kong; Chao Xie; Yunge Tang; Ming Li (Molecular Biology Reports, 2019)

Protective effects of Ganoderma lucidum triterpenoids on oxidative stress and apoptosis in the spleen of chickens induced by cadmium - Xiangqi Teng; Weiqian Zhang; Yangyang Song; Haibin Wang; Ming Ge; Ruili Zhang (Environmental Science and Pollution Research, 2019)

Cloud Radiative Feedbacks during the ENSO Cycle Simulated by CAMS-CSM - Lin Chen; Lijuan Hua; Xinyao Rong; Jian Li; Lu Wang; Guo Zhang; Ming Sun; Zi’an Ge (Journal of Meteorological Research, 2019)

Global trends and future prospects of e-waste research: a bibliometric analysis - Ya Gao; Long Ge; Shuzhen Shi; Yue Sun; Ming Liu; Bo Wang; Yi Shang; Jiarui Wu; Jinhui Tian (Environmental Science and Pollution Research, 2019)

Astaxanthin enhances hematology, antioxidant and immunological parameters, immune-related gene expression, and disease resistance against in Channa argus - Mu-Yang Li; Xin-Yu Liu; Chang-Ge Xia; Gui-Qin Wang; Dong-Ming Zhang (Aquaculture International, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Synergistic effects of environmental regulations on carbon productivity growth in China’s major industrial sectors - Ge Gao; Ke Wang; Chi Zhang; Yi-Ming Wei (Natural Hazards, 2019)

Protective Effect of Ganoderma Triterpenoids on Cadmium-Induced Testicular Toxicity in Chickens - Hongmei Wang; Ruili Zhang; Yangyang Song; Tianqi Li; Ming Ge (Biological Trace Element Research, 2019)

Late Cretaceous basalts and rhyolites from Shimaoshan Group in eastern Fujian Province, SE China: age, petrogenesis, and tectonic implications - Xi-Yao Li; San-Zhong Li; Yan-Hui Suo; Li-Ming Dai; Ling-Li Guo; Feng-Jian Ge; Pei-Jun Lin (International Geology Review, 2018)

TMEM88 mediates inflammatory cytokines secretion by regulating JNK/P38 and canonical Wnt/β-catenin signaling pathway in LX-2 cells - Tao Xu; Lin-xin Pan; Yun-xuan Ge; Peng Li; Xiao-ming Meng; Cheng Huang; Jun Li (Inflammopharmacology, 2018)

Protective Effect of Agaricus blazei Polysaccharide Against Cadmium-Induced Damage on the Testis of Chicken - Yangyang Song; Ruili Zhang; Hongmei Wang; Yan Yan; Ge Ming (Biological Trace Element Research, 2018)

Agaricus blazei Murill Polysaccharides Protect Against Cadmium-Induced Oxidative Stress and Inflammatory Damage in Chicken Spleens - Wanqiu Xie; Ai Lv; Ruyue Li; Zequn Tang; Dexing Ma; Xiaodan Huang; Ruili Zhang; Ming Ge (Biological Trace Element Research, 2018)

Effect of nitrite exposure on oxygen-carrying capacity and gene expression of NF-κB/HIF-1α pathway in gill of bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Wu-Xiao Zhang; Wen-Jing Pan; Hua-Liang Liang; Xian-Ping Ge; Yan-Shun Xu; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou; Si-Lei Xia (Aquaculture International, 2018)

The cephalic morphology of free-living and cave-dwelling species of trechine ground beetles from China (Coleoptera, Carabidae) - Xiao-Zhu Luo; Benjamin Wipfler; Ignacio Ribera; Hong-Bin Liang; Ming-Yi Tian; Si-Qin Ge; Rolf Georg Beutel (Organisms Diversity & Evolution, 2018)

Arg913Gln of SLC12A3 gene promotes development and progression of end-stage renal disease in Chinese type 2 diabetes mellitus - Rong Zhang; Langen Zhuang; Ming Li; Juan zhang; Weijing Zhao; Xiaoxu Ge; Yating Chen; Feng Wang; Niansong Wang; Yuqian Bao; Limei Liu; Yanjun Liu; et al. (Molecular and Cellular Biochemistry, 2018)

Effects of Agaricus blazei Murill Polysaccharide on Cadmium Poisoning on the MDA5 Signaling Pathway and Antioxidant Function of Chicken Peripheral Blood Lymphocytes - Ai Lv; Ming Ge; Xuequan Hu; Wenjing Liu; Guangxing Li; Ruili Zhang (Biological Trace Element Research, 2018)

Miscanthus sp.: Genetic Diversity and Phylogeny in China - Chunxia Ge; Xiuming Liu; Shimin Liu; Jing Xu; Hongfei Li; Tengteng Cui; Yao Yao; Ming Chen; Weili Yu; Cuixia Chen (Plant Molecular Biology Reporter, 2017)

Effects of irrigation management during the rice growing season on soil organic carbon pools - Ying Xu; Ming Zhan; Cougui Cao; Junzhu Ge; Rongzhong Ye; Shaoyang Tian; Mingli Cai (Plant and Soil, 2017)

The accumulation and fractionation of Rare Earth Elements in hydroponically grown Phytolacca americana L. - Ming Yuan; Mei-Na Guo; Wen-Shen Liu; Chang Liu; Antony van der Ent; Jean Louis Morel; Hermine Huot; Wan-Ying Zhao; Xian-Ge Wei; Rong-Liang Qiu; Ye-Tao Tang (Plant and Soil, 2017)

Comparison of white spot syndrome virus infection resistance between Exopalaemon carinicauda and Litopenaeus vannamei under different salinity stresses - Qianqian Ge; Ge Yu; Ming Sun; Jitao Li; Jian Li (Journal of Ocean University of China, 2017)

Study of aircraft icing warning algorithm based on millimeter wave radar - Jinhu Wang; Junxiang Ge; Qilin Zhang; Pan Fan; Ming Wei; Xiangchao Li (Journal of Meteorological Research, 2017)

Bioinformatic prediction and analysis of glucolipid metabolic regulation by miR-34a in Megalobrama amblycephala - Ling-Hong Miao; Wen-Jing Pan; Yan Lin; Xian-Ping Ge; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou (Genes & Genomics, 2017)

The Effects of Agaricus blazei Murill Polysaccharides on Cadmium-Induced Apoptosis and the TLR4 Signaling Pathway of Peripheral Blood Lymphocytes in Chicken - Wenjing Liu; Ming Ge; Xuequan Hu; Ai Lv; Dexing Ma; Xiaodan Huang; Ruili Zhang (Biological Trace Element Research, 2017)

Sharp genetic discontinuity in the aridity‐sensitive Lindera obtusiloba (Lauraceae): solid evidence supporting the Tertiary floral subdivision in East Asia - Jun‐Wei Ye; Wei‐Ning Bai; Lei Bao; Tian‐Ming Wang; Hong‐Fang Wang; Jian‐Ping Ge (Journal of Biogeography, 2017)
Aim Investigating phytogeographical divides can help provide a better understanding of the evolution of floras. Tertiary relict floras in East Asia have been subdivided into a northern region ( NEA ) and a southern region ( SEA ), separated by an arid belt, although this division remains little‐studied since it was proposed in 2002. To test its validity, we investigated the evolutionary history of a Tertiary relict species, Lindera obtusiloba . Location East Asia. Methods Chloroplast DNA (cp DNA ) and nuclear microsatellites ( nSSR s) were genotyped in 34 populations. Regional genetic diversities were compared, and genetic differentiation was calculated between and within regions. Bayesian phylogenetics and Bayesian clustering were employed for phylogeographic reconstruction. The time to the most recent common ancestor ( TMRCA ) and divergence time between the two regions were estimated. Historical rates of gene flow were calculated using the maximum‐likelihood method. The potential habitat at present, during the Last Glacial Maximum ( LGM ) and during the Last Interglacial ( LIG ) were predicted by ecological niche modelling ( ENM ). Results Both markers revealed sharp genetic discontinuities and limited migration between regions. The TMRCA and population divergence can probably both be dated to the Pliocene. Clear genetic structure was found within each region. The genetic diversity of both markers and the age of chlorotypes decreased with increasing longitude within SEA . Japan harboured the highest genetic diversity within NEA , with abundant private and ancestral chlorotypes. NEA had greater genetic diversity than SEA in nSSR s, whereas the opposite was true for cp DNA . ENM in LGM and LIG may support long‐term isolation in multiple locations in both regions. Main conclusions Our study provides solid evidence for the proposed floral subdivision along the arid belt within East Asia. Populations in both regions remained stable over a long period and sustained multiple glacial refugia. Westernmost SEA and easternmost NEA sustained ancestral populations. Clear eastward expansion was detected within SEA .

The Protective Effects of Polysaccharides from Agaricus blazei Murill Against Cadmium-Induced Oxidant Stress and Inflammatory Damage in Chicken Livers - Xuequan Hu; Ruili Zhang; Yingying Xie; Hongmei Wang; Ming Ge (Biological Trace Element Research, 2017)

The emergence of the hyperinvasive vine, Mikania micrantha (Asteraceae), via admixture and founder events inferred from population transcriptomics - Ming Yang; Ziwen He; Yelin Huang; Lu Lu; Yubin Yan; Lan Hong; Hao Shen; Ying Liu; Qiang Guo; Lu Jiang; Yanwu Zhang; Anthony J. Greenberg; et al. (Molecular Ecology, 2017)
Biological invasions that involve well‐documented rapid adaptations to new environments provide unequalled opportunities for testing evolutionary hypotheses. Mikania micrantha Kunth (Asteraceae), a perennial herbaceous vine native to tropical Central and South America, successfully invaded tropical Asia in the early 20th century. It is regarded as one of the most aggressive weeds in the world. To elucidate the molecular and evolutionary processes underlying this invasion, we extensively sampled this weed throughout its invaded range in South‐East and South Asia and surveyed its genetic structure using variants detected from population transcriptomics. Clustering results suggest that more than one source population contributed to this invasion. Computer simulations using genomewide genetic variation support a scenario of admixture and founder events during invasion. The genes differentially expressed between native and invasive populations were found to be involved in oxidative and high light intensity stress responses, pointing to a possible ecological mechanism of adaptation. Our results provide a foundation for further detailed mechanistic and population studies of this ecologically and economically important invasion. This line of research promises to provide new mitigation strategies for invasive species as well as insights into mechanisms of adaptation.

A reliability analysis method for rock slope controlled by weak structural surface - Jia-wen Zhou; Ming-yuan Jiao; Hui-ge Xing; Xing-guo Yang; Yu-chuan Yang (Geosciences Journal, 2017)

A new phenolic glycoside from the stem of Dendrobium nobile - Xue-Ming Zhou; Cai-Juan Zheng; Jia-Ting Wu; Guang-Ying Chen; Bin Zhang; Chong-Ge Sun (Natural Product Research, 2017)

Functional effector memory T cells contribute to protection from superinfection with heterologous simian immunodeficiency virus or simian-human immunodeficiency virus isolates in Chinese rhesus macaques - Ming Sun; Huiwen Zheng; Yingpeng Xie; Bingxiang Li; Haiting Long; Ge Guo; Lei Guo; Jingjing Wang; Ruotong Ning; Yue Li; Longding Liu (Archives of Virology, 2017)

Responses of Dissimilatory Nitrate Reduction to Ammonium and Denitrification to Plant Presence, Plant Species and Species Richness in Simulated Vertical Flow Constructed Wetlands - Chong-Bang Zhang; Wen-Li Liu; Wen-Juan Han; Ming Guan; Jiang Wang; Shu-Yuan Liu; Ying Ge; Jie Chang (Wetlands, 2017)

Challenges and Opportunities with Predicting In Vivo Phase II Metabolism via Glucuronidation From In Vitro Data - Shufan Ge; Yifan Tu; Ming Hu (Current Pharmacology Reports, 2016)

Improved Data Preprocessing Algorithm for Time-Domain Induced Polarization Method with Digital Notch Filter - Shuang-Chao Ge; Ming Deng; Kai Chen; Bin Li; Yuan Li (Acta Geophysica, 2016)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

NF-κB is involved in the LPS-mediated proliferation and apoptosis of MAC-T epithelial cells as part of the subacute ruminal acidosis response in cows - Wen-Jie Fan; He-Ping Li; He-Shui Zhu; Shi-Ping Sui; Pei-Ge Chen; Yue Deng; Tong-Ming Sui; Yue-Ying Wang (Biotechnology Letters, 2016)

Expression of inflammation-related genes in the lung of BALB/c mice response to H7N9 influenza A virus with different pathogenicity - Meng Yu; Qingnan Wang; Wenbao Qi; Kaizhao Zhang; Jianxin Liu; Pan Tao; Shikun Ge; Ming Liao; Zhangyong Ning (Medical Microbiology and Immunology, 2016)

The Syntheses, Structures, Fluorescence Properties and Biological Activity of two Novel Zinc(II) Complexes Controlled by the Tripodal Imidazole Ligand - En-Jun Gao; Shaozhong Zhang; Yang Meng; Fu-Chen Zhao; Xiao-Yu Ma; Hai-Tao Jin; Si-Jia Liu; Jing Ge; Ya-Guang Sun; Wan-zhong Zhang; Ming-Chang Zhu (Journal of Fluorescence, 2016)

Detection of novel adenoviruses in fecal specimens from rodents and shrews in southern China - Xue-yan Zheng; Min Qiu; Xue-mei Ke; Wei-jie Guan; Jin-ming Li; Shu-ting Huo; Shao-wei Chen; Xue-shan Zhong; Wen Zhou; Yi-quan Xiong; Jing Ge; Qing Chen (Virus Genes, 2016)

Molecular cloning, expression, and stress response of the estrogen-related receptor gene (AccERR) from Apis cerana cerana - Weixing Zhang; Ming Zhu; Ge Zhang; Feng Liu; Hongfang Wang; Xingqi Guo; Baohua Xu (The Science of Nature, 2016)

Isolation of prawn (Exopalaemon carinicauda) lipopolysaccharide and β-1, 3-glucan binding protein gene and its expression in responding to bacterial and viral infections - Qianqian Ge; Jian Li; Yafei Duan; Jitao Li; Ming Sun; Fazhen Zhao (Journal of Ocean University of China, 2016)

Curcumin Affects Phase II Disposition of Resveratrol Through Inhibiting Efflux Transporters MRP2 and BCRP - Shufan Ge; Taijun Yin; Beibei Xu; Song Gao; Ming Hu (Pharmaceutical Research, 2016)

Induction of hypoxia-inducible factor-1α by BDNF protects retinoblastoma cells against chemotherapy-induced apoptosis - Yu Gao; Ming Jing; Rongrong Ge; Lili Lang (Molecular and Cellular Biochemistry, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Cloning and Characterization of a Pyruvate Carboxylase Gene from Penicillium rubens and Overexpression of the Genein the Yeast Yarrowia lipolytica for Enhanced Citric Acid Production - Ge-Yi Fu; Yi Lu; Zhe Chi; Guang-Lei Liu; Shou-Feng Zhao; Hong Jiang; Zhen-Ming Chi (Marine Biotechnology, 2016)

The complete mitochondrial genome of fall armyworm Spodoptera frugiperda (Lepidoptera:Noctuidae) - Qiu-Ning Liu; Xin-Yue Chai; Dan-Dan Bian; Bao-Ming Ge; Chun-Lin Zhou; Bo-Ping Tang (Genes & Genomics, 2016)

Isolation and characterization of twenty-two polymorphic microsatellite markers from Gardenia jasminoides (Rubiaceae) - YAN-QIN XU; GUO-YAN WEI; YIN ZHOU; FEI GE; GUANG-MING LUO (Journal of Genetics, 2015)

Virulence differences among Sclerotinia sclerotiorum isolates determines host cotyledon resistance responses in Brassicaceae genotypes - Xin Tian Ge; Ming Pei You; Martin J. Barbetti (European Journal of Plant Pathology, 2015)

A two‐domain protein triggers heat shock pathway and necrosis pathway both in model plant and nematode - Lifang Ruan; Huihui Wang; Ge Cai; Donghai Peng; Hua Zhou; Jinshui Zheng; Lei Zhu; Xixi Wang; Haoquan Yu; Seng Li; Ce Geng; Ming Sun (Environmental Microbiology, 2015)
Summary The entomopathogen B acillus thuringiensis is equipped with multiple virulent factors. The genome sequence of B . thuringiensis YBT 1520 revealed the presence of a two‐domain protein named Nel which is composed of a necrosis‐inducing phytophthora protein 1‐like domain found in phytopathogens and a ricin B ‐like lectin domain. The merging of two distantly related domains is relatively rare. Nel induced necrosis and pathogen‐triggered immunity ( PTI ) on model plants. The Nel also exhibited inhibition activity to nematode. Microscopic observation showed that the toxicity of Nel to nematodes targets the intestine. Quantitative proteomics revealed that Nel stimulated the host defence. The Nel thus possesses dual roles, as both toxin and elicitor. Remarkably, the Nel protein triggered a similar response, induction of the heat shock pathway and the necrosis pathway, in both model plants and nematodes. The unusual ability of Nel to function across kingdom suggests a highly conserved mechanism in eukaryotes that predates the divergence of plants and animal. It is also speculated that the two‐domain protein is the result of horizontal gene transfer ( HGT) between phytopathogens and entomopathogens. Our results provide an example that HGT occurs between members of different species or even genera with lower frequency are particularly important for evolution of new bacterial pathogen lineages with new virulence. B acillus thuringiensis occupies the same ecological niches, plant and soil, as phytopathogens, providing the opportunity for gene exchange.

Population genetic structure of Oryza rufipogon and Oryza nivara : implications for the origin of O. nivara - Rong Liu; Xiao‐Ming Zheng; Lian Zhou; Hai‐Fei Zhou; Song Ge (Molecular Ecology, 2015)
Ecological speciation plays a primary role in driving species divergence and adaptation. Oryza rufipogon and Oryza nivara are two incipient species at the early stage of speciation with distinct differences in morphology, life history traits and habitat preference, and therefore provide a unique model for the study of ecological speciation. However, the population genetic structure of the ancestral O. rufipogon has been controversial despite substantial study, and the origin of the derivative O. nivara remains unclear. Here, based on sequences of 10 nuclear and two chloroplast loci from 26 wild populations across the entire geographic ranges of the two species, we conducted comprehensive analyses using population genetics, phylogeography and species distribution modelling ( SDM ) approaches. In addition to supporting the two previously reported major subdivisions, we detected four genetically distinct groups within O. rufipogon and found no correlation between the genetic groups and either species identity or geographical regions. The SDM clearly showed substantial change in the distribution range of O. rufipogon in history, demonstrating that the repeated extinction and colonization of local populations due to multiple glacial–interglacial cycles during the Quaternary was most likely the main factor shaping the confounding population genetic structure of O. rufipogon . Moreover, we found significant differences between the two species in climate preferences, suggestive of an important role for climatic factors in the adaptation, persistence and expansion of O. nivara . Finally, based on the genetic pattern and dynamics of the O. nivara populations, we hypothesize that O. nivara might have independently originated multiple times from different O. rufipogon populations.

Prestack forward modeling of tight reservoirs based on the Xu–White model - Chao Zhu; Qing-Xin Guo; Qing-Shun Gong; Zhan-Guo Liu; Sen-Ming Li; Ge-Ping Huang (Applied Geophysics, 2015)

The E23K and A190A variations of the KCNJ11 gene are associated with early-onset type 2 diabetes and blood pressure in the Chinese population - Langen Zhuang; Yu Zhao; Weijing Zhao; Ming Li; Ming Yu; Ming Lu; Rong Zhang; Xiaoxu Ge; Taishan Zheng; Can Li; Jun Yin; Jingyuan Yin; et al. (Molecular and Cellular Biochemistry, 2015)

Low-frequency data analysis and expansion - Jun-Hua Zhang; Bin-Bin Zhang; Zai-Jin Zhang; Hong-Xian Liang; Da-Ming Ge (Applied Geophysics, 2015)

Transgenic expression of human cytoxic T-lymphocyte associated antigen4-Immunoglobulin (hCTLA4Ig) by porcine skin for xenogeneic skin grafting - Yong Wang; Hua-Qiang Yang; Wen Jiang; Na-Na Fan; Ben-Tian Zhao; Zhen Ou-Yang; Zhao-Ming Liu; Yu Zhao; Dong-Shan Yang; Xiao-Yang Zhou; Hai-Tao Shang; Lu-Lu Wang; et al. (Transgenic Research, 2015)

Spatiotemporal Dynamics of Salt Marsh Vegetation regulated by Plant Invasion and Abiotic Processes in the Yangtze Estuary: Observations with a Modeling Approach - Zhen-Ming Ge; Li-Quan Zhang; Lin Yuan (Estuaries and Coasts, 2015)

Expression Profile of Maize MicroRNAs Corresponding to Their Target Genes Under Drought Stress - Ying-Ge Wang; Ming An; Shu-Feng Zhou; Yue-Hui She; Wan-Chen Li; Feng-Ling Fu (Biochemical Genetics, 2014)

A convenient four-component one-pot synthesis of 2-amino-1,3,4-thiadiazoles in water - Peng Liu; Ao-Ze Su; Yuan-Qiang Wang; Ze-Mei Ge; Tie-Ming Cheng; Run-Tao Li (Molecular Diversity, 2014)

Association between the MMP-9−1562 C>T polymorphism and the risk of stroke: a meta-analysis - Zhen-Zhen Fan; Zhao-Ming Ge; Hong-Bin Cai; Zhi-Yan Liu; Pei Liu; Hao-Yue Wang (Molecular Biology Reports, 2014)

Remarkable reductions of PAKs in the brain tissues of scrapie-infected rodent possibly linked closely with neuron loss - Ge Meng; Chan Tian; Hui Wang; Yin Xu; Bao-Yun Zhang; Qi Shi; Chen Gao; Cao Chen; Xue-Yu Fan; Jing Wang; Kang Xiao; Ke Ren; et al. (Medical Microbiology and Immunology, 2014)

Spectrum analysis of wind profiling radar measurements - Zheng Ruan; Ruiqi Mu; Ming Wei; Runsheng Ge (Journal of Meteorological Research, 2014)

Salicylic Acid Enhances Resistance to Fusarium oxysporum f. sp. phaseoli in Common Beans (Phaseolus vulgaris L.) - Ren Feng Xue; Jing Wu; Lan Fen Wang; Matthew W. Blair; Xiao Ming Wang; Wei De Ge; Zhen Dong Zhu; Shu Min Wang (Journal of Plant Growth Regulation, 2014)

A tripeptide (NSK) inhibits Japanese encephalitis virus infection in vitro and in vivo - Chen Li; Ling-ling Ge; Ya-ling Yu; Li Huang; Yue Wang; Ming-xia Sun; Hassan Ishag; Liang-xiao Ma; Xue-hua Li; Zhi-qiang Shen; Xiang Mao (Archives of Virology, 2014)

The comparison of sensitivity of motion sickness between retinal degeneration fast mice and normal mice - Xiao-Cheng Wang; Zhao-Hui Shi; Ka Bian; Lei Zhang; Jun-Hui Xue; Guo-Qing Yang; Xue-Song Ge; Zuo-Ming Zhang (Journal of Comparative Physiology A, 2014)

Molecular and biochemical characterization of Sclerotinia sclerotiorum laboratory mutants resistant to dicarboximide and phenylpyrrole fungicides - Ya-Bing Duan; Chang-Yan Ge; Ming-Guo Zhou (Journal of Pest Science, 2014)

Analysis of the microphysical properties of a stratiform rain event using an L-Band profiler radar - Zheng Ruan; Hu Ming; Jianli Ma; Runsheng Ge; Lingen Bian (Journal of Meteorological Research, 2014)

Assessment of social vulnerability to natural hazards in the Yangtze River Delta, China - Yi Ge; Wen Dou; Zhihui Gu; Xin Qian; Jinfei Wang; Wei Xu; Peijun Shi; Xiaodong Ming; Xin Zhou; Yuan Chen (Stochastic Environmental Research and Risk Assessment, 2013)

Isolation and characterization of fifteen polymorphic tetranucleotide microsatellite loci in Schizopygopsis younghusbandi Regan - Huan Zheng; Gui-Rong Zhang; Shan-Shan Guo; Kai-Jian Wei; Cong-Xin Xie; Tai-Ming Ge (Conservation Genetics Resources, 2013)

Association of CDKN1B gene polymorphisms with susceptibility to breast cancer: a meta-analysis - Heping Xiang; He Li; Weiwei Ge; Weidong Wu; Ming Gao; Wei Wang; Lei Hong; Datong Jiang; Changle Zhang (Molecular Biology Reports, 2013)

Association between interferon gamma +874 T>A polymorphism and acute renal allograft rejection: evidence from published studies - Yu-Zheng Ge; Ran Wu; Rui-Peng Jia; Hao Liu; Peng Yu; Yan Zhao; Yu-Ming Feng (Molecular Biology Reports, 2013)

Effects of perfluorooctanesulfonate and perfluorobutanesulfonate on the growth and sexual development of Xenopus laevis - Qin-Qin Lou; Yin-Feng Zhang; Zhen Zhou; Ya-Li Shi; Ya-Nan Ge; Dong-Kai Ren; Hai-Ming Xu; Ya-Xian Zhao; Wu-Ji Wei; Zhan-Fen Qin (Ecotoxicology, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Microparameter Prediction for a Triaxial Compression PFC3D Model of Rock Using Full Factorial Designs and Artificial Neural Networks - Miao-jun Sun; Hui-ming Tang; Xin-li Hu; Yun-feng Ge; Sha Lu (Geotechnical and Geological Engineering, 2013)

Quantification of serum HBXAP DNA in lung cancer patients by quantitative fluorescent polymerase chain reaction - Yu-Lei Hou; Hui Chen; Ming-Jian Ge; Feng-Zeng Li; Cheng-Jun Xue; Yan-Feng Wu; Hai-Xia Luo (Molecular Biology Reports, 2013)

Effects of Elevated CO2 and Temperature on Biomass Growth and Allocation in a Boreal Bioenergy Crop (Phalaris arundinacea L.) from Young and Old Cultivations - Chao Zhang; Zhen-Ming Ge; Seppo Kellomäki; Kai-Yun Wang; Jin-Nan Gong; Xiao Zhou (BioEnergy Research, 2013)

Adaptive management to climate change for Norway spruce forests along a regional gradient in Finland - Zhen-Ming Ge; Seppo Kellomäki; Heli Peltola; Xiao Zhou; Hannu Väisänen (Climatic Change, 2013)

Impacts of climate change on primary production and carbon sequestration of boreal Norway spruce forests: Finland as a model - Zhen-Ming Ge; Seppo Kellomäki; Heli Peltola; Xiao Zhou; Hannu Väisänen; Harri Strandman (Climatic Change, 2013)

Characteristics, causes and mitigation of catastrophic debris flow hazard on 21 July 2011 at the Longda Watershed of Songpan County, China - Yong-gang Ge; Peng Cui; Xiao-jun Guo; Guo-hu Song; Wei-ming Liu (Journal of Mountain Science, 2013)

Seasonal migration by a large forest ungulate: a study on takin (Budorcas taxicolor) in Sichuan Province, China - Tian-Pei Guan; Bao-Ming Ge; William J. McShea; Sheng Li; Yan-Ling Song; Chad M. Stewart (European Journal of Wildlife Research, 2013)

The development of EST-SSR markers in Lilium regale and their cross-amplification in related species - Suxia Yuan; Liang Ge; Chun Liu; Jun Ming (Euphytica, 2013)

Thaxtomin A-deficient endophytic Streptomyces sp. enhances plant disease resistance to pathogenic Streptomyces scabies - Lan Lin; Hui Ming Ge; Tong Yan; Yan Hua Qin; Ren Xiang Tan (Planta, 2012)

Erratum to: Seasonal Physiological Responses and Biomass Growth in a Bioenergy Crop (Phalaris arundinacea L.) Under Elevated Temperature and CO2, Subjected to Different Water Regimes in Boreal Conditions - Zhen-Ming Ge; Seppo Kellomäki; Xiao Zhou; Heli Peltola; Kai-Yun Wang; Pertti J. Martikainen (BioEnergy Research, 2012)

Association of IL23R polymorphisms with psoriasis and psoriatic arthritis: a meta-analysis - Kun-Ju Zhu; Cheng-Yao Zhu; Ge Shi; Yi-Ming Fan (Inflammation Research, 2012)

Seasonal physiological responses and biomass growth in a bioenergy crop (Phalaris arundinacea L.) under elevated temperature and CO2, subjected to different water regimes in boreal conditions - Zhen-Ming Ge; Seppo Kellomäki; Xiao Zhou; Heli Peltola; Kai-Yun Wang; Pertti J. Martikainen (BioEnergy Research, 2012)

Genome-wide Identification and Characterization of a Dehydrin Gene Family in Poplar (Populus trichocarpa) - Chang-Cai Liu; Chun-Ming Li; Bao-Guang Liu; Su-Jie Ge; Xiu-Mei Dong; Wei Li; Hang-Yong Zhu; Bai-Chen Wang; Chuan-Ping Yang (Plant Molecular Biology Reporter, 2012)

An efficient three-component, one-pot synthesis of 2-alkylthio-4-amino-5-cyano-6-aryl(alkyl)pyrimidines in water - Qiao-Yan Li; Ze-Mei Ge; Tie-Ming Cheng; Run-Tao Li (Molecular Diversity, 2012)

Relationship of summer soil moisture with early winter monsoon and air temperature over eastern China - Ge Liu; Jun‐Ming Chen; Li‐Ren Ji; Shu‐Qing Sun (International Journal of Climatology, 2012)
The time‐lagged effect of summer soil moisture (SM) on ensuing winter climate in eastern China is examined. The East Asian winter monsoon (EAWM) in early winter (November) and associated air temperature over eastern China are shown to significantly correlate with the previous summer (June–August) SM in eastern China with a center located at the lower reaches of the Yellow River (LRYR). The positive anomalies of summer SM, persisting for a few months, may act as a buffer to defer the ground cooling of eastern China in early winter mainly through modulating thermal capacity. And the warmer ground of eastern China could lead to a warmer air temperature above the ground through direct land–air interactions and through indirectly adjusting the EAWM which is sensitive to the land–sea thermal contrast. These results provide an empirical predictor for the EAWM and for the variability of air temperature over eastern China in early winter. Copyright © 2011 Royal Meteorological Society

Heat shock transcription factor 1 inhibits H2O2-induced cardiomyocyte death through suppression of high-mobility group box 1 - Ying Yu; Ming Liu; Lei Zhang; Quan Cao; Peipei Zhang; Hong Jiang; Yunzeng Zou; Junbo Ge (Molecular and Cellular Biochemistry, 2012)

PDGF-AA Mediates B104CM-Induced Oligodendrocyte Precursor Cell Differentiation of Embryonic Neural Stem Cells Through Erk, PI3K, and p38 Signaling - Jian-Guo Hu; Yan-Xia Wang; Hong-Ju Wang; Ming-Sheng Bao; Zhen-Huan Wang; Xin Ge; Feng-Chao Wang; Jian-Sheng Zhou; He-Zuo Lü (Journal of Molecular Neuroscience, 2012)

Norcantharidin, a protective therapeutic agent in renal tubulointerstitial fibrosis - Ying Li; Yan Ge; Fu You Liu; You Ming Peng; Lin Sun; Jun Li; Qiong Chen; Yan Sun; Kun Ye (Molecular and Cellular Biochemistry, 2012)

A meta-analysis of β1-adrenergic receptor gene polymorphisms in idiopathic dilated cardiomyopathy - Bo Jin; Qu-Zhen Ge-Shang; Yong Li; Wei Shen; Hai-Ming Shi; Huan-Chun Ni (Molecular Biology Reports, 2012)

The therapeutic potential of G-CSF in pressure overload induced ventricular reconstruction and heart failure in mice - Ji Ming Li; Zhi Feng Yao; Yun Zeng Zou; Jun Bo Ge; Ai Li Guan; Jian Wu; Shou Ling Mi; Yan Yan Liang; Zhen Ma (Molecular Biology Reports, 2012)

Major Pollutants in Soils of Abandoned Agricultural Land Contaminated by e-Waste Activities in Hong Kong - Brenda Natalia Lopez; Yu Bon Man; Yin Ge Zhao; Jin Shu Zheng; Anna Oi Wah Leung; Jun Yao; Ming Hung Wong (Archives of Environmental Contamination and Toxicology, 2011)

Genetic diversity and domestication history of African rice (Oryza glaberrima) as inferred from multiple gene sequences - Zhi-Ming Li; Xiao-Ming Zheng; Song Ge (Theoretical and Applied Genetics, 2011)

Alkaline-stress response in Glycine soja leaf identifies specific transcription factors and ABA-mediated signaling factors - Ying Ge; Yong Li; De-Kang Lv; Xi Bai; Wei Ji; Hua Cai; Ao-Xue Wang; Yan-Ming Zhu (Functional & Integrative Genomics, 2011)

Rhizobium sphaerophysae sp. nov., a novel species isolated from root nodules of Sphaerophysa salsula in China - Lin Xu; Jian Feng Shi; Peng Zhao; Wei Min Chen; Wei Qin; Ming Tang; Ge Hong Wei (Antonie van Leeuwenhoek, 2011)

Varied association of prothrombin G20210A polymorphism with coronary artery disease susceptibility in different ethnic groups: evidence from 15,041 cases and 21,507 controls - Bo Jin; Yong Li; Qu-Zhen Ge-Shang; Huan-Chun Ni; Hai-Ming Shi; Wei Shen (Molecular Biology Reports, 2011)

Heat shock transcription factor-1 inhibits H2O2-induced apoptosis via down-regulation of reactive oxygen species in cardiac myocytes - Lei Zhang; Hong Jiang; Xiaoqing Gao; Yunzeng Zou; Ming Liu; Yanyan Liang; Ying Yu; Weidong Zhu; Haozhu Chen; Junbo Ge (Molecular and Cellular Biochemistry, 2011)

Effects of Elevated CO2 on Growth and Nutrient Uptake of Eichhornia crassipe Under Four Different Nutrient Levels - Jun-Zhi Liu; Ya-Ming Ge; Yu-Fei Zhou; Guang-Ming Tian (Water, Air, & Soil Pollution, 2010)

Phylogeny of Salsoleae s.l. (Chenopodiaceae) based on DNA sequence data from ITS, psbB–psbH, and rbcL, with emphasis on taxa of northwestern China - Zhi-Bin Wen; Ming-Li Zhang; Ge-Lin Zhu; Stewart C. Sanderson (Plant Systematics and Evolution, 2010)

Ecological divergence in the presence of gene flow in two closely related Oryza species (Oryza rufipogon and O. nivara) - XIAO-MING ZHENG; SONG GE (Molecular Ecology, 2010)

Detecting relationships between amylose content and amino acid contents of indica rice with conditional approach - Chun Hai Shi; Qiong Qiong Zhu; Ke Ming Wang; Guo Ke Ge; Jian Guo Wu; Zhen Ghao Xu (Journal of Genetics, 2010)

Sanchi ginseng (Panax notoginseng (Burkill) F. H. Chen) in China: distribution, cultivation and variations - Hong Bo Guo; Xiu Ming Cui; Na An; Ge Ping Cai (Genetic Resources and Crop Evolution, 2010)

Magnetic cell sorting and flow cytometry sorting methods for the isolation and function analysis of mouse CD4+ CD25+ Treg cells - Hang Yan; Chen-guang Ding; Pu-xun Tian; Guan-qun Ge; Zhan-kui Jin; Li-ning Jia; Xiao-ming Ding; Xiao-ming Pan; Wu-jun Xue (Journal of Zhejiang University-SCIENCE B, 2009)

The contribution of proline residues to protein stability is associated with isomerization equilibrium in both unfolded and folded states - Meng Ge; Xian-Ming Pan (Extremophiles, 2009)

Characterization of an early gene orf122 from Bombyx mori nucleopolyhedrovirus - Jun-Qing Ge; Jin-Fang Zhao; Ya-Ming Shao; Cai-Hong Tian; Chuan-Xi Zhang (Molecular Biology Reports, 2009)

Cloning and functional analysis of wheat V-H+-ATPase subunit genes - Qian Zhao; Yan-Jun Zhao; Bao-Cun Zhao; Rong-Chao Ge; Ming Li; Yin-Zhu Shen; Zhan-Jing Huang (Plant Molecular Biology, 2009)

Refolding of the hyperthermophilic protein Ssh10b involves a kinetic dimeric intermediate - Meng Ge; Yong-Jin Mao; Xian-Ming Pan (Extremophiles, 2009)

The involvement of sortase A in high virulence of STSS-causing Streptococcus suis serotype 2 - Changjun Wang; Ming Li; Youjun Feng; Feng Zheng; Yaqing Dong; Xiuzhen Pan; Gong Cheng; Ruiping Dong; Dan Hu; Xiaodan Feng; Junchao Ge; Di Liu; et al. (Archives of Microbiology, 2009)

Contrasting population genetic structure and gene flow between Oryza rufipogon and Oryza nivara - Hai-Fei Zhou; Xiao-Ming Zheng; Ruo-Xun Wei; Gerard Second; Duncan A. Vaughan; Song Ge (Theoretical and Applied Genetics, 2008)

Distribution, sources, and potential risk of polycyclic aromatic hydrocarbons (PAHs) in drinking water resources from Henan Province in middle of China - Ying-ge Ma; Jin-ping Cheng; Fei Jiao; Ke-xin Duo; Zheng Rong; Ming Li; Wen-hua Wang (Environmental Monitoring and Assessment, 2008)

One new cinnamic imide dervative from the fruits of Tribulus terrestris - A-Li Lv; Nan Zhang; Min-Ge Sun; Yong-Fu Huang; Yi Sun; Hong-Yu Ma; Hui-Ming Hua; Yue-Hu Pei (Natural Product Research, 2008)

Development of thirteen microsatellite loci for Impatiens lateristachys (Balsaminaceae) - Lin-Feng Li; Guo-Qing Chen; Yong-Ming Yuan; Xue-Jun Ge (Conservation Genetics, 2008)

Strong Genetic Differentiation of Primula sikkimensis in the East Himalaya–Hengduan Mountains - Feng-Ying Wang; Xue-Jun Ge; Xun Gong; Chi-Ming Hu; Gang Hao (Biochemical Genetics, 2008)

Development and characterization of microsatellite markers for an endangered shrub, Ammopiptanthus mongolicus (Leguminosae) and cross-species amplification in Ammopiptanthus nanus - Guo-Qing Chen; Hong-Wen Huang; Ming Kang; Xue-Jun Ge (Conservation Genetics, 2007)

Induction and origin of adventitious shoots from chimeras of Brassica juncea and Brassica oleracea - Xue-Yun Zhu; Man Zhao; Sheng Ma; Ya-Ming Ge; Ming-Fang Zhang; Li-Ping Chen (Plant Cell Reports, 2007)

Fermentation of pretreated sugarcane bagasse hemicellulose hydrolysate to ethanol by Pachysolen tannophilus - Ke-Ke Cheng; Jing-Ping Ge; Jian-An Zhang; Hong-Zhi Ling; Yu-Jie Zhou; Ming-De Yang; Jing-Ming Xu (Biotechnology Letters, 2007)

Biological Comparison of Two Genotypes of Helicoverpa armigera Single-Nucleocapsid Nucleopolyhedrovirus - Zhong-Jian Guo; Jun-Qing Ge; Dun Wang; Ya-Ming Shao; Qi-Yi Tang; Chuan-Xi Zhang (BioControl, 2006)

Artificial synthesis of interspecific chimeras between tuber mustard (Brassica juncea) and cabbage (Brassica oleracea) and cytological analysis - Li-Ping Chen; Ya-Ming Ge; Xue-Yun Zhu (Plant Cell Reports, 2006)

A clinical and molecular-genetic analysis of Chinese patients with lattice corneal dystrophy and novel Thr538Pro mutation in theTGFBI (BIGH3) gene - Ping Yu; Yangshun Gu; Yuehong Yang; Xiaoyi Yan; Liu Chen; Zhen Ge; Ming Qi; Jianmin Si; Lei Guo (Journal of Genetics, 2006)

FPF1 transgene leads to altered flowering time and root development in rice - Ming-Li Xu; Jia-Fu Jiang; Lei Ge; Yun-Yuan Xu; Hui Chen; Yuan Zhao; Yu-Rong Bi; Jiang-Qi Wen; Kang Chong (Plant Cell Reports, 2005)

Effect of brassinolide on callus growth and regeneration in Spartina patens (Poaceae) - Zhou Lu; Min Huang; Dong-Ping Ge; Yong-Hua Yang; Xiao-Ning Cai; Pei Qin; Jian-Ming She (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Transport of protons and lactate in cultured human fetal retinal pigment epithelial cells - Steffen Hamann; Morten la Cour; Ge Ming Lui; Magnus Bundgaard; Thomas Zeuthen (Pflügers Archiv - European Journal of Physiology, 2000)

Retrieval single-doppler radar wind with variational assimilation method-part i: objective selection of functional weighting factors - Wei Ming; Dang Renqing; Ge Wenzhong; Takao Takeda (Advances in Atmospheric Sciences, 1998)

Allozyme Variation in Ophiopogon xylorrhizus , an Extreme Endemic Species of Yunnan, China - Song Ge; Da‐Ming Zhang; Hai‐Qun Wang; Guang‐Yuan Rao (Conservation Biology, 1997)

Numerical analysis and case experiment for forecasting capability by using high accuracy moisture advectional algorithm - Xiaozhen Ge; Feng Li; Ming Ge (Meteorology and Atmospheric Physics, 1997)